Lithium-ion secondary battery

By forming a specific compositional cover layer on the surface of the positive electrode active material of the lithium-ion secondary battery, the problem of degradation of the cycle characteristics when the charging voltage is increased is solved, and high capacity and high safety battery performance is achieved.

JP7656651B2Active Publication Date: 2025-04-03SEMICON ENERGY LAB CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023082049
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-05-22
Filing Date
2023-05-18
Publication Date
2025-04-03
Estimated Expiration
2037-10-11

AI Technical Summary

Technical Problem

When the existing lithium-ion secondary batteries increase the charging voltage, the cycle characteristics are reduced, making it difficult to improve capacity and safety at the same time.

Method used

A positive electrode active material composed of lithium, transition metal, oxygen, magnesium, fluorine and oxygen is used, and a cover layer is formed on the surface of the surface, and the surface concentration of magnesium and fluorine is within a specific range through X-ray photoelectron spectroscopy measurement.

Benefits of technology

It effectively suppresses the reduction of the capacity of the positive electrode active substance in the charge and discharge cycle, improves the charge and discharge characteristics and safety of the battery, and maintains a high capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656651000014
    Figure 0007656651000014
  • Figure 0007656651000015
    Figure 0007656651000015
  • Figure 0007656651000016
    Figure 0007656651000016
Patent Text Reader

Abstract

To provide a positive electrode active material that is used for a lithium ion secondary battery to suppress the decrease in capacity in a charging and discharging cycle.SOLUTION: In a surface layer part of a positive electrode active material, a coating layer is formed by segregation. The positive electrode active material includes a first region and a second region. The first region exists internally. The second region exists in a part of the surface layer part and the inside. The first region contains lithium, transition metal, and oxygen. The second region contains magnesium, fluorine, and oxygen.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] One aspect of the present invention relates to an article, a method, or a manufacturing method. Alternatively, the present invention relates to a process, Pertaining to a machine, manufacture, or composition of matter. One embodiment of the present invention is a semiconductor device, a display device, a light-emitting device, a power storage device, a lighting device, or an electronic In particular, the present invention relates to a positive electrode active material that can be used in a secondary battery, a secondary battery, and and an electronic device having a secondary battery.

[0002] In this specification, the term "electricity storage device" refers to elements and devices having an electricity storage function in general. For example, lithium ion secondary batteries and other storage batteries (also called secondary batteries) These include lithium ion capacitors and electric double layer capacitors.

[0003] In addition, in this specification, the term "electronic device" refers to any device having a power storage device. Electro-optical devices having a power storage device, and information terminal devices having a power storage device are all electronic devices. [Background technology]

[0004] In recent years, various types of storage devices such as lithium-ion secondary batteries, lithium-ion capacitors, and air batteries have become available. The development of lithium-ion secondary batteries, which have high output and capacity, is particularly popular. Mobile phones, smartphones, notebook computers and other portable information terminals, portable music devices Players, digital cameras, medical equipment, or hybrid vehicles (HEVs), electric vehicles ( Next-generation clean energy such as electric vehicles (EV) or plug-in hybrid vehicles (PHEV) Demand for rechargeable energy has expanded rapidly along with the development of the semiconductor industry, including automobiles. It has become an indispensable source of information in today's information society.

[0005] Currently, the characteristics required for lithium-ion secondary batteries are higher capacity and cycle time. These include improved module characteristics, safety in various operating environments, and improved long-term reliability.

[0006] It is known that one way to increase the capacity of a lithium-ion secondary battery is to increase the charging voltage. For example, cobalt oxide, which is often used as the positive electrode active material in lithium-ion secondary batteries, The capacity of lithium is generally 155mAh / g when the charging voltage is 4.3V, If the charging voltage is increased to 4.6 V, the capacity becomes 220 mAh / g (see Figure 21(A)).

[0007] However, it is also known that increasing the charging voltage deteriorates the cycle characteristics. For example, the capacity of a typical lithium cobalt oxide battery after 30 cycles when the charging voltage is 4.4V is The capacity retention rate is over 95%, but when the charging voltage is increased to 4.6V, the capacity retention rate after 30 cycles is The ownership rate will fall to below 50% (see Figure 21(B)).

[0008] Therefore, in order to improve the cycle characteristics and increase the capacity of lithium-ion secondary batteries, Improvements to the material have been investigated (Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2012-018914 A [Patent Document 2] JP 2016-076454 A Summary of the Invention [Problem to be solved by the invention]

[0010] As described above, lithium ion secondary batteries and the positive electrode active materials used therein have the following characteristics: capacity, size, There is still room for improvement in various aspects, such as the charge / discharge characteristics, reliability, safety, and cost. It has been done.

[0011] One embodiment of the present invention is to improve the efficiency of charge / discharge cycles by using the same in a lithium ion secondary battery. Another object of the present invention is to provide a positive electrode active material in which the decrease in the amount of the positive electrode active material is suppressed. Another object of the present invention is to provide a high-capacity secondary battery. Another object of the present invention is to provide a secondary battery having excellent charge and discharge characteristics. An object of the present invention is to provide a secondary battery with high safety and reliability.

[0012] Another embodiment of the present invention provides a novel substance, an active material, a power storage device, or a manufacturing method thereof. One of our goals is to provide

[0013] The description of these problems does not preclude the existence of other problems. It is not necessary for the embodiment to solve all of these problems. It is possible to extract problems other than those mentioned above from the description of the claim. [Means for solving the problem]

[0014] In order to achieve the above object, one aspect of the present invention provides a method for producing a cathode active material having a surface layer that is damaged by segregation. It is characterized by forming a covering layer.

[0015] One embodiment of the present invention is a positive electrode active material, the positive electrode active material including a first region, a second region, and The first region is present inside the positive electrode active material, and the second region is present in the surface layer portion and the positive electrode active material. and a portion of the interior, the first region having lithium, a transition metal, and oxygen, and the second region having The region A is a positive electrode active material having magnesium, fluorine, and oxygen.

[0016] Another embodiment of the present invention is a positive electrode active material, the positive electrode active material comprising lithium, a transition metal, and , oxygen, magnesium, and fluorine, and is present on the surface of the positive electrode active material; and of atoms including lithium, transition metals, oxygen, fluorine, and magnesium as measured by spectroscopy The total amount is 100 atomic %, and it is present on the surface of the positive electrode active material and measured by X-ray photoelectron spectroscopy. The magnesium concentration is 1 atomic % or more and 16 atomic % or less, and fluorine is The positive electrode active material has a concentration of 0.2 atomic % or more and 4 atomic % or less.

[0017] Another embodiment of the present invention is a positive electrode active material, the positive electrode active material comprising lithium, a transition metal, and , oxygen, magnesium, and fluorine, and the positive electrode active material is measured by X-ray photoelectron spectroscopy. The ratio of magnesium concentration to fluorine concentration on the surface is Mg:F=y:1 (3≦y≦5). , which is a positive electrode active material.

[0018] Another embodiment of the present invention is a positive electrode active material, the positive electrode active material comprising lithium, a transition metal, and , oxygen, magnesium, and fluorine, and the positive electrode active material is measured by X-ray photoelectron spectroscopy. The peak position of the surface fluorine binding energy is 682 eV or more and less than 685 eV. It is a positive electrode active material.

[0019] In the above, the transition metal preferably includes cobalt. Preferably, the transition metals include manganese, cobalt and nickel.

[0020] Another aspect of the present invention is a positive electrode active material, the positive electrode active material having a first region and a second region. a first region is present therein and comprises lithium, a transition metal, and oxygen; It has a layered rock salt type crystal structure, and the second region exists in the surface layer and part of the interior, and is composed of magnesium. The crystal structure of the crystal is a rock-salt crystal structure having a first region and a second region. The crystal orientation of the positive electrode active material surface is consistent with that of the positive electrode active material. The ratio of the Mg concentration to the fluorine concentration is Mg:F=y:1 (3≦y≦5).

[0021] In the above, the bond energy of fluorine on the surface of the positive electrode active material measured by X-ray photoelectron spectroscopy It is preferable that the peak position is 682 eV or more and less than 685 eV.

[0022] In addition, one embodiment of the present invention is a method for producing a fluorine-containing gas-liquid crystal comprising the steps of: mixing a lithium source, a transition metal source, a magnesium source, and a fluorine source; and heating the mixture at 800° C. or more and 1100° C. or less for 2 hours or more and 20 hours or less. Heating in an oxygen-containing atmosphere at 500°C to 1200°C for a holding time of 50 hours or less and a step of preparing a positive electrode active material, The atomic ratio of magnesium contained in the magnesium source is Mg:F=1:x (1.5≦x≦4). , a method for producing a positive electrode active material.

[0023] Alternatively, one embodiment of the present invention is a positive electrode active material, the positive electrode active material including a first region and a second region. and a region, the first region being present inside the positive electrode active material and the second region being present outside the positive electrode active material. The first region is present in the surface layer and a part of the inside, and contains lithium, cobalt, and oxygen. The second region has cobalt, magnesium, fluorine, and oxygen, and is a positive electrode active material. When the first region was analyzed by electron energy loss spectroscopy, the L3 / L 2 is less than 3.8, and the cobalt in the second region has an L3 / L2 ratio of 3.8 or more; It is a positive electrode active material. Effect of the Invention

[0024] According to one embodiment of the present invention, by using the compound in a lithium ion secondary battery, It is possible to provide a positive electrode active material in which the capacity reduction caused by the charging is suppressed. It is also possible to provide a secondary battery having excellent charge / discharge characteristics. In addition, a secondary battery having high safety and reliability can be provided. A substance, a power storage device, or a method for manufacturing the same can be provided. [Brief description of the drawings]

[0025] [Figure 1] FIG. 1 illustrates an example of a positive electrode active material. [Diagram 2] 1A to 1C illustrate an example of a method for manufacturing a positive electrode active material. [Diagram 3] FIG. 13 is a cross-sectional view of an active material layer in the case where a graphene compound is used as a conductive assistant. [Figure 4] FIG. 2 is a diagram illustrating a coin-type secondary battery. [Diagram 5] FIG. 2 is a diagram illustrating a cylindrical secondary battery. [Figure 6] 1A and 1B are diagrams illustrating examples of secondary batteries. [Figure 7] 1A and 1B are diagrams illustrating examples of secondary batteries. [Figure 8] 1A and 1B are diagrams illustrating examples of secondary batteries. [Figure 9] 1A and 1B are diagrams illustrating examples of secondary batteries. [Figure 10] FIG. 1 is a diagram illustrating a laminated secondary battery. [Figure 11] FIG. 1 is a diagram illustrating a laminated secondary battery. [Figure 12] FIG. 2 is a diagram showing the appearance of a secondary battery. [Figure 13] FIG. 2 is a diagram showing the appearance of a secondary battery. [Figure 14] 1A to 1C are diagrams illustrating a method for manufacturing a secondary battery. [Figure 15] 1A and 1B are diagrams illustrating a bendable secondary battery. [Figure 16] 1A and 1B are diagrams illustrating a bendable secondary battery. [Figure 17] 1A to 1C are diagrams illustrating examples of electronic devices. [Figure 18] 1A to 1C are diagrams illustrating examples of electronic devices. [Figure 19] 1A to 1C are diagrams illustrating examples of electronic devices. [Figure 20] 1A to 1C are diagrams illustrating examples of electronic devices. [Figure 21] FIG. 13 is a diagram illustrating the characteristics of a secondary battery according to a conventional example. [Figure 22] 2 shows a STEM image and EDX mapping of the positive electrode active material of Example 1. [Diagram 23] 2 shows a STEM image and EDX mapping of the positive electrode active material of Example 1. [Figure 24] 4 is a graph showing the amount of magnesium near the surface of the positive electrode active material of Example 1. [Diagram 25] 3 is a graph showing cycle characteristics of the secondary battery of Example 1. [Figure 26] 3 is a graph showing cycle characteristics of the secondary battery of Example 1. [Figure 27] 3 is a graph showing cycle characteristics of the secondary battery of Example 1. [Figure 28] 3 is a graph showing cycle characteristics of the secondary battery of Example 1. [Figure 29] 1 is a STEM image of the positive electrode active material of Example 2. [Diagram 30] 1 is a STEM image of the positive electrode active material of Example 2. [Diagram 31] 6 is a graph showing the charge / discharge characteristics of the secondary battery of Example 2. [Diagram 32] 6 is a graph showing cycle characteristics of the secondary battery of Example 2. [Diagram 33] 4A and 4B are STEM and FFT images of the positive electrode active material of Example 3. [Diagram 34] 4A and 4B are STEM and FFT images of the positive electrode active material of Example 3. [Diagram 35] 4 is a STEM image and EDX mapping of the positive electrode active material of Example 3. [Diagram 36] TEM image of the positive electrode active material of Example 3. [Figure 37] 4 is a STEM image and EDX mapping of the positive electrode active material of Example 3. [Figure 38] 4 is a ToF-SIMS depth analysis of the positive electrode active material of Example 3. [Figure 39] 13 is an XPS spectrum of the positive electrode active material of Example 3. [Diagram 40] 10 is a graph showing cycle characteristics of the secondary battery of Example 4. [Diagram 41] 10 is a graph showing cycle characteristics of the secondary battery of Example 4. [Diagram 42] 10 is a graph showing cycle characteristics of the secondary battery of Example 4. [Diagram 43] 13 is a graph showing cycle characteristics of the secondary battery of Example 6. [Diagram 44] 1 is a STEM image of the positive electrode active material of Example 6. [Diagram 45] 1 is a STEM image of the positive electrode active material of Example 6. [Figure 46] 13A and 13B are STEM and FFT images of the positive electrode active material of Example 6. [Figure 47] 1 shows a STEM image and an estimated model of the crystal structure of the positive electrode active material of Example 6. [Figure 48] 13 is a STEM image and EDX mapping of the positive electrode active material of Example 6. [Figure 49] 13 is a STEM image and EDX mapping of the positive electrode active material of Example 6. [Figure 50] 13 is a graph showing the results of EELS analysis of the positive electrode active material of Example 7. [Figure 51] 13 is a graph showing the results of EELS analysis of the positive electrode active material of Example 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. The present invention is not limited to the following description, and various modifications in form and details are possible by those skilled in the art. The present invention is not limited to the description of the following embodiments. It is not something that can be done.

[0027] In each of the drawings described in this specification, the positive electrode, the negative electrode, the active material layer, the separator, the exterior body, etc. The size and thickness of each component may be exaggerated for clarity of description. Therefore, each component is not necessarily limited by its size, and the correlation between each component is not necessarily limited by its size. It is not limited to the relative size.

[0028] In addition, in the configuration of the present invention described in this specification, etc., the same parts or parts having similar functions The same reference numerals are used in common between different drawings, and the repeated explanations are omitted. When referring to parts having similar functions, the same hatch pattern is used and no special reference numerals are attached. There may not be.

[0029] In addition, the crystal planes and directions are expressed using Miller indices. In the above, numbers are preceded by a superscript bar. However, in this specification, etc., due to the restrictions on the notation in the application, In addition, individual directions that indicate directions within a crystal are indicated by [ ], and the equivalent The collective orientation, which indicates all directions, is indicated by < >, and the individual faces, which indicate crystal faces, are indicated by ( ), and the equivalent symmetries are indicated by The aggregate faces that each have will be indicated by {}.

[0030] In this specification, segregation refers to a phenomenon in which a solid consisting of multiple elements (e.g., A, B, C) This refers to the phenomenon in which a certain element (such as B) is distributed unevenly.

[0031] In the present specification and the like, the layered rock-salt type crystal structure of a composite oxide containing lithium and a transition metal is The structure has a rock-salt type ion arrangement in which cations and anions are arranged alternately, and the transition metal and lithium The lithium atoms are regularly arranged to form a two-dimensional plane, allowing two-dimensional diffusion of lithium. The term refers to a crystal structure. It is acceptable for there to be defects such as deficiencies of cations or anions. Strictly speaking, the rock salt crystal structure is a distorted structure of the rock salt crystal lattice. be.

[0032] The rock salt crystal structure is a structure in which cations and anions are arranged alternately. There may be a deficiency of on or an anion.

[0033] Layered rock salt crystals and anions in rock salt crystals form a cubic close-packed structure (face-centered cubic lattice structure). When layered rock salt crystals come into contact with each other, the cubic close-packed structure of anions is formed. However, the space group of the layered rock salt crystal is R-3m. Since the space group is different from that of the rock salt type Fm-3m, the crystal plane index that satisfies the above conditions is the layered rock. In this specification, layered rock salt type crystals and rock salt type crystals are different. When the orientation of the cubic close-packed structure formed by the anions is aligned, the crystal orientation is roughly uniform. We can say that we will.

[0034] For example, lithium cobalt oxide having a layered rock salt type crystal structure and When magnesium oxide comes into contact with lithium cobalt oxide, the crystal orientation is roughly the same. When the (1-1-4) plane of the lithium cobalt oxide contacts the {001} plane of the magnesium oxide, When the (104) face of magnesium is in contact with the {001} face of magnesium oxide, lithium cobalt oxide When the (0-14) plane of the lithium cobalt oxide contacts the {001} plane of the magnesium oxide, When the (001) plane of the lithium cobalt oxide contacts the {111} plane of the magnesium oxide, For example, when the (012) plane is in contact with the {111} plane of magnesium oxide.

[0035] The crystal orientation of the two regions roughly coincides, as can be seen from TEM (transmission electron microscope) and STEM images. (Scanning Transmission Electron Microscope) Image, HAADF-STEM (High Angle Scattering Annular Dark Field Scanning Transmission Electron Microscope) This can be judged from images such as ABF-STEM (annular bright-field scanning transmission electron microscope) images. X-ray diffraction, electron diffraction, neutron diffraction, etc. can also be used as materials for judgment. TE In M images, the arrangement of cations and anions can be observed as repeated bright and dark lines. When the orientation of the cubic close-packed structure of the crystalline rock salt crystals and the rock salt crystals is aligned, bright lines and It is possible to observe that the angle between the repeated dark lines is 5 degrees or less, and more preferably 2.5 degrees or less. In addition, light elements such as oxygen and fluorine may not be clearly observed in TEM images. In some cases, the alignment can be determined by the arrangement of the metal elements.

[0036] In this specification, the similarity of the structure of a two-dimensional interface is called epitaxy. Crystal growth that resembles the structure of a two-dimensional interface is called epitaxial growth. Topotaxis refers to the fact that molecules have similar fundamental structures or have the same crystallographic orientation. Therefore, in the case of topotaxis, when a part of a cross section is observed, two regions (for example For example, the crystal orientation of the underlying region and the region that is grown is roughly the same.

[0037] (Embodiment 1) [Positive electrode active material structure] First, a positive electrode active material 100 according to one embodiment of the present invention will be described with reference to FIG. As shown in FIG. 1, the positive electrode active material 100 has a first region 101 and a second region 102. It may be said that the second region 102 is disposed on the first region 101, or the second region 102 It may be said that the first region 101 is at least partially covered.

[0038] The first region 101 and the second region 102 are regions having different compositions. As described later, the region 102 is preferably a region in which a specific element is segregated. In FIG. 1(A), the boundary between the first region 101 and the second region 102 may not be clear. The dotted line divides the region 102, and the gradient of the concentration of an element across the dotted line is shown in gray. In FIG. 1B and subsequent figures, the boundary between the first region 101 and the second region 102 is shown as a solid line for the sake of convenience. The boundary between the first region 101 and the second region 102 is shown only by a dotted line. will be discussed later.

[0039] As shown in FIG. 1B, a second region 102 may be present inside the positive electrode active material. For example, when the first region 101 is polycrystalline, a specific element segregates at and near the grain boundaries. In addition, the second region 102 may be formed. A specific element may be segregated in and around the second region 102. In the specification, crystal defects are defects that can be observed in TEM images, etc., and the inclusion of other elements in the crystal. This refers to structures that incorporate

[0040] As shown in FIG. 1B, the second region 102 covers the entire first region 101. It doesn't have to be.

[0041] In other words, the first region 101 exists inside the positive electrode active material 100, and the second region 10 The second region 102 is present in the surface layer of the positive electrode active material 100. It may be present inside 00.

[0042] The first region 101 may be referred to as, for example, solid phase A. The second region 102 may be referred to as, for example, solid phase B. For example, it may be called solid phase B.

[0043] If the particle size of the positive electrode active material 100 is too large, it becomes difficult for lithium to diffuse. On the other hand, if the size is too small, the surface of the active material layer becomes too rough. There are also problems such as the active material layer becoming difficult to support when applied to the body and excessive reaction with the electrolyte. Therefore, D50 (also called the median diameter) is 0.1 μm or more and 100 μm or less. is preferable, and the thickness is more preferably 1 μm or more and 40 μm or less.

[0044] <First Area 101> The first region 101 includes lithium, a transition metal, and oxygen. It may be said that the material has a composite oxide containing lithium and a transition metal.

[0045] The transition metal contained in the first region 101 is a layered rock salt type composite oxide together with lithium. It is preferable to use a metal capable of forming the above-mentioned metals. For example, manganese, cobalt, nickel, etc. In other words, the transition metal in the first region 101 and Cobalt alone may be used, or both cobalt and manganese may be used. Alternatively, the first region 101 may be formed of three types of metals, i.e., zinc, manganese, and nickel. In addition, metals other than transition metals, such as aluminum, may be contained.

[0046] That is, the first region 101 is made of lithium cobalt oxide, lithium nickel oxide, and a part of cobalt. Lithium cobalt oxide with manganese substitution, lithium nickel-manganese-cobalt oxide Lithium-cobalt-lithium aluminate and other composites containing lithium and transition metals It may have an oxide.

[0047] The first region 101 functions as a region of the positive electrode active material 100 that particularly contributes to the charge / discharge reaction. In order to increase the capacity when the positive electrode active material 100 is used in a secondary battery, the first region Preferably, 101 has a larger volume than the second region 102 .

[0048] Since lithium easily diffuses two-dimensionally in the layered rock salt crystal structure, the first region 101 is preferably made of the layered rock salt crystal structure. Moreover, when the first region 101 has a layered rock-salt type crystal structure, it is unexpectedly preferable that As described later, magnesium is prone to segregation. However, the first region 101 is entirely made up of layered rocks. The crystal structure may not be a salt type. For example, the first region 101 may have a crystal defect. Alternatively, a portion of the first region 101 may be amorphous or have another crystal structure. It's fine.

[0049] <Second Region 102> The second region 102 includes magnesium, fluorine, and oxygen. Region 102 has magnesium oxide, and some of the oxygen may be replaced with fluorine. stomach.

[0050] The second region 102 covers at least a part of the first region 101. The magnesium oxide in 02 is an electrochemically stable material, so it can withstand repeated charging and discharging. It is therefore suitable as a coating layer since it is resistant to deterioration even under high temperatures.

[0051] If the second region 102 is too thin, its function as a covering layer is reduced, but if it is too thick, the second region 102 cannot be easily covered. Therefore, the thickness of the second region is preferably 0.5 nm or more and 50 nm or less. , and more preferably 0.5 nm or more and 3 nm or less.

[0052] If the second region 102 has a rock salt type crystal structure, the crystal orientation will be the same as that of the first region 101. This is preferable because it is easy to adhere to the second region 10 and it is easy to function as a stable coating layer. The entire second region 102 does not have to have a rock-salt crystal structure. The crystal structure may be of the same or different crystal structure.

[0053] In general, the positive electrode active material loses transition metals such as cobalt and manganese as it is repeatedly charged and discharged. Side reactions occur, such as dissolution into the electrolyte, oxygen release, and the crystal structure becoming unstable. However, the positive electrode active material 100 according to one embodiment of the present invention has a second layer in the surface layer. Since the first region 101 has the region 102, the composite oxide containing lithium and a transition metal contained in the first region 101 is It is possible to make the crystal structure of the object more stable.

[0054] The second region 102 contains magnesium, fluorine, and oxygen, and further contains the first It is preferable that the first region 101 and the second region 102 have the same transition metal. If the regions 102 have the same transition metal, the valence of the transition metal will be different in the two regions. More specifically, the transition metal in the first region 101 is preferably a trivalent atom. It is preferable that the second region 102 has more transition metals with a valence of 2 than atoms with other valences. It is preferred that there are more atoms of the other valence.

[0055] When the second region 102 contains a large amount of divalent transition metals, CoO(II), MnO(II), Ni( II) There are many metal oxides with a transition metal:oxygen ratio of 1:1 (atomic ratio). The metal oxide of forms a stable solid solution with magnesium oxide, which is also an oxide of a divalent metal. Therefore, the second region 102 can become a more stable and excellent covering layer.

[0056] The valence of transition metals can be determined by EELS (electron energy loss spectroscopy) and XAFS (X-ray absorption fine structure). analysis), XPS (X-ray photoelectron spectroscopy), ESR (electron spin resonance), Mössbauer spectroscopy, etc. Among them, EELS has a high spatial resolution, so the second region 102 This is preferable because it allows analysis of even thin layers of only a few nm.

[0057] When analyzing the valence of transition metals by EELS, the valence can be determined by the ratio of L3 / L2. The larger the L3 / L2 ratio, the higher the proportion of divalent transition metals. When the transition metals in the first region 101 and the second region 102 were analyzed, The L3 / L2 ratio of the transition metal in the second region 102 is less than 3.8. It is preferable that / L2 is 3.8 or more.

[0058] In addition to the above, the second region 102 may also contain lithium.

[0059] In addition, if a second region 102 exists inside the first region 101 as shown in FIG. The crystal structure of the composite oxide containing lithium and a transition metal in the first region 101 is further stabilized. This is preferable because it may be possible to stabilize the concentration.

[0060] The fluorine in the second region 102 exists in a bond state other than MgF2 and LiF. Specifically, when the surface of the positive electrode active material 100 is analyzed by XPS, fluorine The peak position of the bond energy between and other elements is 682 eV or more and less than 685 eV It is preferable that the electron transport energy is about 684.3 eV, and more preferable that the electron transport energy is about 684.3 eV. The bond energy does not match either of these.

[0061] In this specification, the peak position of the bond energy of a certain element when analyzed by XPS This means that the intensity of the energy spectrum is maximum in the range corresponding to the bond energy of the element. This refers to the value of bond energy such that

[0062] <Boundary between the first area 101 and the second area 102> The first area 101 and the second area 102 are used for TEM images, STEM images, and FFT (Fast Fourier Transform) images. Energy dispersive X-ray (EDX) analysis, Time of Flight SIMS (Time of Flight Secondary Depth analysis by ion mass spectrometry, XPS (X-ray photoelectron spectroscopy), Auger electron spectroscopy It can be confirmed that the material has a different composition using optical spectroscopic methods, TDS (thermal desorption spectrometry), etc. For example, in the cross-sectional TEM and STEM images of the positive electrode active material 100, the difference in the constituent elements Since the difference in brightness is observed, the constituent elements of the first region 101 and the second region 102 It can be seen that the first region 101 and the second region 102 are different. It can be observed that 102 has different elements. However, it is not necessarily the first one that is identified by various analyses. It is not necessary that a clear boundary between the first region 101 and the second region 102 is observable.

[0063] In this specification and the like, the range of the second region 102 present in the surface layer portion of the positive electrode active material 100 is The magnesium concentration detected by depth direction analysis from the outermost surface of the positive electrode active material 100 is The depth direction analysis is performed using the EDX line analysis described above. and depth-direction analysis using ToF-SIMS. The peak of the concentration of Zn exists within a depth of 2 nm from the surface to the center of the positive electrode active material 100. It is preferable that the depth of the pores is within 1 nm, and more preferable that the depth of the pores is within 0.5 nm. It is more preferable that the magnesium concentration is present at a depth of 1 / 5 of the peak. That is, the range of the second region 102 varies depending on the manufacturing method. Generally, the thickness is from 2 nm to 5 nm from the surface of the positive electrode active material.

[0064] The second region 102 present inside the first region 101 was also detected by the depth profile analysis. This refers to the region where the magnesium concentration measured is 1 / 5 or more of the peak.

[0065] The distribution of fluorine in the positive electrode active material 100 preferably overlaps with the distribution of magnesium. Therefore, the peak of the fluorine concentration increases in the depth direction from the surface of the positive electrode active material 100 toward the center. Preferably, the pores are present at a depth of up to 2 nm, more preferably at a depth of up to 1 nm. , and more preferably to a depth of up to 0.5 nm.

[0066] In this way, the second region 102 is formed by dispersing magnesium from the surface of the positive electrode active material 100 toward the inside. It can also be said to be a concentration gradient region in which the concentrations of aluminum and fluorine decrease.

[0067] Magnesium and fluorine concentrations were determined by ToF-SIMS, XPS, Auger electron spectroscopy, It can be analyzed by TDS, etc.

[0068] In addition, the measurement range of XPS is about 5 nm from the surface of the positive electrode active material 100. It is possible to quantitatively analyze the concentration of elements present in the region from 10 to 5 nm. When the thickness of the second region 102 is less than 5 nm, a part of the second region 102 and the first region 101 are combined. When the thickness of the second region 102 is 5 nm or more from the surface, the original thickness of the second region 102 is The surface of the positive electrode active material 100 was analyzed by XPS to quantitatively analyze the lithium concentration. The atoms in the first region 101 include transition metals, oxygen, fluorine, and magnesium. Magnesium concentration is 1 atomic% or more when the total amount is 100 atomic%. 16 atomic % or less, and the fluorine concentration is 0.2 atomic % or more and 4 atomic % or less. The ratio of magnesium to fluorine is preferably Mg:F=y: The atomic ratio is preferably 1 (3≦y≦5), and Mg:F is about 4:1. When the magnesium concentration and the fluorine concentration are within these ranges, the secondary battery When used in this manner, the positive electrode active material 100 can exhibit extremely favorable cycle characteristics.

[0069] As mentioned above, the concentrations of magnesium and fluorine gradually decreased from the surface to the inside. Therefore, the first region 101 has an element, such as magnesium, that the second region 102 has. Similarly, the second region 102 may have the same elements as the first region 101. The first region 101 may also include carbon, sulfur, silicon, sodium, calcium, salt, etc. The second region 102 may contain other elements such as carbon, sulfur, and zirconium. It contains other elements such as yellow, silicon, sodium, calcium, chlorine, and zirconium. This is also fine.

[0070] [Segregation] The second region 102 may be formed by a liquid phase method such as sputtering, a solid phase method, or a sol-gel method. However, the present inventors have found that the method using a magnesium source and a fluorine source After mixing with the heat generating material, the magnesium is segregated by heating to form the second region 102. Furthermore, it has been revealed that the second region 102 formed in this manner can be obtained. It was revealed that the positive electrode active material has extremely excellent properties.

[0071] For example, in Example 4 of Patent Document 2 (JP 2016-076454 A), magnesium Then, a powder of the composite oxide is mixed with lithium fluoride. By heating, the surface of the composite oxide is fluorinated and lithiated to form a surface oxide. The method states that no magnesium was detected in the surface oxide.

[0072] However, the present inventors have found that the magnesium source and the fluorine source are mixed together as starting materials. By this, it was possible to cause magnesium oxide to segregate in the surface layer portion of the positive electrode active material 100. In addition, it was found that fluorine added to the starting material has the effect of segregating magnesium. The inventors clarified.

[0073] In order to form the second region 102 by segregation of magnesium, the surface layer portion of the positive electrode active material 100 In addition, magnesium may segregate at grain boundaries and their vicinity, and at crystal defects and their vicinity. The second region 102 formed at and near the grain boundary or at and near the crystal defect is Further stabilization of the crystal structure of the composite oxide containing lithium and transition metals in region 101 of 1 This could contribute to the

[0074] In order to effectively perform the segregation in the second region 102, the concentrations of magnesium and fluorine in the raw material are Mg :F=1:x (1.5≦x≦4) (atomic ratio), Mg:F=1:2 It is more preferable that the ratio is about (atomic number ratio).

[0075] On the other hand, the concentrations of magnesium and fluorine in the second region 102 resulting from the segregation are M It is preferable that g:F=y:1 (3≦y≦5) (atomic ratio), and Mg:F=about 4:1. It is even more preferable that the thickness is 100 nm or more.

[0076] The second region 102 formed by segregation is formed by epitaxial growth. Therefore, the crystal orientations of the first region 101 and the second region 102 may partly roughly coincide with each other. That is, the first region 101 and the second region 102 may be topotaxis. When the crystal orientations of the region 101 and the second region 102 are roughly the same, the second region 102 is It may function as a better covering layer.

[0077] <Third Area 103> In the above examples, the positive electrode active material 100 has the first region 101 and the second region 102. However, one embodiment of the present invention is not limited thereto. For example, as shown in FIG. The positive electrode active material 100 may have a third region 103. The third region 103 may be, for example, For example, the third region 102 may be provided so as to be in contact with at least a portion of the second region 102. The region 103 may be a coating containing carbon, such as a graphene compound, or a lithium compound. The third region 103 may be a coating having a decomposition product of the electrolyte or aluminium. In the case of a coating having such a structure, the positive electrode active material 100 itself and the positive electrode active material 100 and the current collector are electrically conductive. In addition, the third region 103 can be used to improve the electrical conductivity of the battery. In the case of a coating having such a structure, excessive reaction with the electrolyte is suppressed, and the cycle is improved when the coating is used in a secondary battery. The characteristics of the filter can be improved.

[0078] Furthermore, a buffer region may be provided between the first region 101 and the second region 102. The buffer region may contain, for example, titanium, aluminum, in addition to lithium, transition metals, and oxygen. The buffer region preferably contains a metal such as zirconium or vanadium. The first region 101 may overlap with the second region 102. When the crystal structure of the first region 101 and the second region 102 is set to the quality 100, the crystal structure of the first region 101 and the second region 102 is further stabilized. Furthermore, it is possible to provide a positive electrode active material having excellent cycle characteristics, which is preferable.

[0079] [Production method] The semiconductor device has a first region 101 and a second region 102, and the second region 102 is formed by segregation. A method for producing the positive electrode active material 100 in this case will be described with reference to FIG. When the transition metal contained in the first region 101 is cobalt, that is, when the first region 101 is cobalt, The case of lithium barium oxide is explained. In addition, magnesium oxide is segregated. The case of forming the second region 102 containing fluorine will be described.

[0080] First, starting materials are prepared (S11). Specifically, a lithium source, a cobalt source, a magnesium source, The lithium source is, for example, lithium carbonate, Lithium fluoride, lithium hydroxide, etc. can be used. Examples of the cobalt source include Cobalt oxide, cobalt hydroxide, cobalt oxyhydroxide, cobalt carbonate, cobalt oxalate As the magnesium source, for example, Magnesium, magnesium fluoride, etc. can be used as the fluorine source. For example, lithium fluoride, magnesium fluoride, etc. can be used. Magnesium can be used as both a lithium source and a fluorine source, and magnesium fluoride can be used as both a lithium source and a fluorine source. The magnesium can be used as both a magnesium source and a fluorine source.

[0081] In this embodiment, lithium carbonate (Li2CO3) is used as the lithium source, and cobalt is used as the cobalt source. Cobalt oxide (Co3O4), magnesium oxide (MgO) as a magnesium source, lithium Lithium fluoride (LiF) will be used as the uranium source and fluorine source.

[0082] The atomic ratio of magnesium and fluorine in the raw materials is Mg:F=1:x(1.5≦x≦4) (atom It is preferable that Mg:F is about 1:2 (atomic ratio), and more preferable that Mg:F is about 1:2 (atomic ratio). The ratio of magnesium oxide to lithium fluoride is MgO:LiF=1:x(1.5≦x≦4)( The molar ratio of MgO:LiF is preferably about 1:2. This is more preferable.

[0083] The molar ratio of each raw material can be, for example, as follows: 1 / 2·Li2CO3+((1-z) / 3)·Co3O4+z·MgO+2z·LiF (z=0.01)

[0084] Next, the weighed starting materials are mixed (S12). For example, a ball mill or a bead mill may be used for mixing. etc. can be used.

[0085] Next, the materials mixed in S12 are heated (S13). This process is distinguished from the subsequent heating process. Therefore, it is sometimes called the first heating or firing. The first heating is performed at a temperature of 800°C or higher and 1050°C or lower. It is preferable to carry out the treatment at a temperature of 900°C or lower, and more preferably at a temperature of 900°C or higher and 1000°C or lower. The heating time is preferably 2 hours or more and 20 hours or less. It is preferable to carry out the process in a dry atmosphere. A dry atmosphere has a dew point of -50°C or less. It is preferable that the temperature is -100°C or lower, and more preferable that the temperature is -100°C or lower. The temperature was increased by 200°C / h and dry air with a dew point of -109°C was blown for 10 hours. The flow rate will be L / min.

[0086] By the first heating in S13, the composite material including lithium and a transition metal in the first region 101 is formed. This first heating process also synthesizes the magnesium oxide contained in the starting material. Some of the lithium and fluorine segregate to the surface layer of the composite oxide containing lithium and transition metals. At this point, most of the magnesium and fluorine are in the form of complex oxides containing lithium and transition metals. It is in a solid solution state.

[0087] Next, the material heated in S13 is cooled to room temperature (S14). The cooling time is the same as or shorter than the heating time. For example, it is recommended to carry out the test for 10 to 15 hours. After cooling, the synthesized material is preferably sieved. In this embodiment, the mixture is sieved using a 53 μm mesh.

[0088] The starting materials are lithium, cobalt, fluorine, and magnesium, which are synthesized in advance. In this case, steps S12 to S14 may be used. can be omitted.

[0089] Next, the material cooled in S14 is subjected to a second heating (S15). In order to distinguish between the first and second heating, it is sometimes called the second heating or annealing. Optimal conditions for the second heating The particle size and composition of the composite oxide containing lithium, cobalt, fluorine, and magnesium It depends on the temperature, but it is preferable to hold the temperature for 50 hours or less, and 2 hours or more. It is more preferable to perform the treatment for 10 hours or less. The specified temperature is 500°C or higher and 1200°C or lower. Preferably, the temperature is 700° C. or higher and 1000° C. or lower, more preferably, about 800° C. It is also preferable to heat the material in an atmosphere containing oxygen. In this embodiment, the material is heated at 800° C. The heating time was set to 2 hours, with the temperature rising at 200℃ / h and 10L / h of dry air with a dew point of -109℃. It will be run at min.

[0090] By performing the second heating in S15, the magnesium and fluorine contained in the starting material are converted into lithium. This can promote segregation of the titanium and transition metal in the surface layer of the composite oxide.

[0091] Finally, the material heated in S15 is cooled to room temperature. The cooling time is equal to or greater than the heating time. It is preferable to carry out the cooling process over a period of time. Then, the cooled material is collected (S16) and the first region is A positive electrode active material 100 having a first region 101 and a second region 102 can be obtained.

[0092] By using the positive electrode active material described in this embodiment, a secondary battery with high capacity and good cycle characteristics can be obtained. This embodiment may be used in appropriate combination with other embodiment modes. This can be done.

[0093] (Embodiment 2) In this embodiment, a secondary battery having the positive electrode active material 100 described in the previous embodiment is used. In this embodiment, the positive electrode, the negative electrode, and the electrode The following description will be given taking as an example a secondary battery in which the electrolyte is enclosed in an exterior body.

[0094] [Positive electrode] The positive electrode has a positive electrode active material layer and a positive electrode current collector.

[0095] <Cathode active material layer> The positive electrode active material layer includes a positive electrode active material. The positive electrode active material layer also includes a conductive assistant and a binder.

[0043]

[0096] As the positive electrode active material, the positive electrode active material 100 described in the previous embodiment can be used. By using the positive electrode active material 100 described in the previous embodiment, it is possible to obtain a high capacity and good cycle characteristics. This makes it possible to produce an excellent secondary battery.

[0097] As the conductive assistant, a carbon material, a metal material, a conductive ceramic material, or the like can be used. In addition, a fibrous material may be used as the conductive assistant. The content of the electrical auxiliary agent is preferably 1 wt% or more and 10 wt% or less, and more preferably 1 wt% or more and 5 wt% or less. is more preferred.

[0098] The conductive additive can form an electrically conductive network in the electrode. This makes it possible to maintain a path of electrical conduction between the positive electrode active materials. By adding the agent, an active material layer having high electrical conductivity can be realized.

[0099] Examples of the conductive assistant include natural graphite, artificial graphite such as mesocarbon microbeads, and carbon fibers. Examples of carbon fibers that can be used include mesophase pitch carbon fibers. In addition, carbon fibers such as isotropic pitch-based carbon fibers can be used. Carbon nanofibers and carbon nanotubes can be used. The tube can be produced by, for example, a vapor phase growth method. For example, carbon black (acetylene black (AB) etc.), graphite particles Carbon materials such as copper, nickel, and graphene can be used. Nickel, aluminum, silver, gold and other metal powders, metal fibers, conductive ceramic materials, etc. It can be used.

[0100] In addition, a graphene compound may be used as the conductive assistant.

[0101] Graphene compounds have excellent electrical properties, such as high electrical conductivity, as well as high flexibility and In addition, graphene may have excellent physical properties such as high mechanical strength. The compound has a planar shape. Graphene compounds enable surface contact with low contact resistance. In addition, even if the material is thin, it can have very high conductivity, and a small amount of the material can be used to efficiently conduct electricity within the active material layer. Therefore, the graphene compound can be used as a conductive additive. This is preferable because it is possible to increase the contact area between the active material and the conductive assistant. In this case, the graphene compound is preferably a graphene compound having a low electrical resistance. For example, graphene or multi-graphene or reduced graphene O It is particularly preferred to use RGO oxide. This refers to a compound obtained by reducing graphene oxide (GO).

[0102] When using an active material with a small particle size, for example, an active material with a particle size of 1 μm or less, the specific surface area of ​​the active material is Therefore, a large amount of conductive additive is required. This tends to result in a relatively reduced amount of active material carried. If the capacity of the secondary battery decreases, the capacity of the secondary battery decreases. When graphene compounds are used, they efficiently form conductive paths even in small amounts. This is particularly preferable because it is possible to avoid reducing the amount of the active material carried.

[0103] In the following, as an example, a graphene compound is used as a conductive assistant in the active material layer 200. An example of the cross-sectional structure will be described.

[0104] 3A shows a vertical cross-sectional view of the active material layer 200. The active material layer 200 is made of granular positive electrode active material. 100, a graphene compound 201 as a conductive assistant, and a binder (not shown). Here, the graphene compound 201 may be, for example, graphene or multi-graphene. Here, the graphene compound 201 preferably has a sheet shape. In addition, the graphene compound 201 may include a plurality of multi-graphenes or (and) a plurality of The graphene may be partially overlapped to form a sheet.

[0105] In the vertical cross section of the active material layer 200, as shown in FIG. In FIG. 3(A), the sheet-like graphene compound 201 is dispersed almost uniformly. The graphene compound 201 is shown in bold in schematic form, but in reality it is a single or multiple layer of carbon molecules. The graphene compounds 201 are thin films having a thickness of 100 nm. The positive electrode active material 100 is wrapped or covered with the positive electrode active material 100 or on the surface of the positive electrode active material 100. Since they are formed to stick to each other, they are in surface contact with each other.

[0106] Here, a plurality of graphene compounds are bonded to each other to form a mesh-like graphene compound. The graphene compound is then bonded to the graphene sheet (hereinafter referred to as a graphene compound net or a graphene net). When the active material is covered with a graphene net, the graphene net can bond the active material to each other. It can also function as a binder to bind the material together. This allows the amount of binder to be reduced. The ratio of active material to the electrode volume or weight can be adjusted to suit the application. In other words, the capacity of the power storage device can be increased.

[0107] Here, graphene oxide is used as the graphene compound 201, and is mixed with an active material to form an active material. After the layer that will become the layer 200 is formed, it is preferable to reduce it. By using graphene oxide, which has extremely high dispersibility in polar solvents, The mixture 201 can be dispersed approximately uniformly inside the active material layer 200. The solvent is removed by evaporation from the dispersion medium containing the dispersed graphene oxide, and the graphene oxide is reduced. Therefore, the graphene compounds 201 remaining in the active material layer 200 are partially overlapped with each other. By dispersing the particles so that they are in surface contact with each other, a three-dimensional conductive path can be formed. The reduction of graphene oxide may be performed, for example, by heat treatment or by using a reducing agent. This is also possible.

[0108] Therefore, unlike granular conductive additives such as acetylene black, which come into point contact with the active material, graphite Since the compound 201 enables surface contact with low contact resistance, it is more effective than ordinary conductive additives. The amount of the positive electrode active material 100 and the graphene compound 201 is reduced, and the electrical conductivity between the positive electrode active material 100 and the graphene compound 201 is improved. Therefore, the ratio of the positive electrode active material 100 in the active material layer 200 can be increased. This makes it possible to increase the discharge capacity of the power storage device.

[0109] Examples of binders include styrene-butadiene rubber (SBR) and styrene-isoprene. Acrylonitrile-styrene rubber, butadiene rubber, ethylene-styrene rubber, acrylonitrile-butadiene rubber, butadiene rubber, It is preferable to use a rubber material such as a propylene-diene copolymer. Fluorine rubber can be used.

[0110] As the binder, it is preferable to use, for example, a water-soluble polymer. As the molecule, for example, polysaccharides can be used. CMC, methyl cellulose, ethyl cellulose, hydroxypropyl cellulose Cellulose derivatives such as cellulose, diacetyl cellulose, regenerated cellulose, and starch These water-soluble polymers can be used in combination with the above-mentioned rubber materials. It is even better if there is a

[0111] Alternatively, the binder may be polystyrene, polymethyl acrylate, or polymethyl methacrylate. Polyvinyl chloride (Polymethyl methacrylate (PMMA)), Sodium polyacrylate, Polyvinyl chloride Polyvinyl alcohol (PVA), polyethylene oxide (PEO), polypropylene oxide, Polyimide, polyvinyl chloride, polytetrafluoroethylene, polyethylene, polypropylene Polyethylene, isobutylene, polyethylene terephthalate, nylon, polyvinylidene fluoride ( PVdF), polyacrylonitrile (PAN), ethylene propylene diene polymer, poly It is preferable to use materials such as polyvinyl acetate and nitrocellulose.

[0112] The binder may be used in combination of two or more of the above.

[0113] For example, a material having a particularly excellent viscosity adjusting effect may be used in combination with other materials. For example, rubber materials have excellent adhesive strength and elasticity, but it is difficult to adjust the viscosity when mixed with a solvent. In such cases, for example, it is possible to mix the material with a particularly excellent viscosity adjusting effect. As a material having a particularly excellent viscosity adjusting effect, for example, a water-soluble polymer is preferably used. In addition, examples of water-soluble polymers that are particularly effective in adjusting viscosity include the aforementioned polysaccharides, such as calcium carbonate. Carboxymethylcellulose (CMC), methylcellulose, ethylcellulose, hydroxy Cellulose derivatives such as propyl cellulose, diacetyl cellulose, and regenerated cellulose For example, starch or starch can be used.

[0114] In addition, cellulose derivatives such as carboxymethyl cellulose are, for example, carboxymethyl The solubility of cellulose increases when it is converted into a salt such as sodium salt or ammonium salt. It is easy to exert its effect as a viscosity adjuster. The higher the solubility, the easier it is to make the electrode slurry. In the preparation of the electrode, the dispersibility of the electrode with the active material and other components can be improved. In this regard, the cellulose and cellulose derivatives used as the binder for the electrodes are as follows: These salts are also included.

[0115] Water-soluble polymers stabilize the viscosity by dissolving in water, and also serve as active materials and binders. Other materials to be combined, such as styrene butadiene rubber, are stable in aqueous solution. In addition, since it has a functional group, it is easy to stably adsorb on the surface of the active material. It is expected that cellulose derivatives such as carboxymethyl cellulose, for example, For example, many materials have functional groups such as hydroxyl groups and carboxyl groups. It is expected that the polymers will interact with each other and widely cover the surface of the active material.

[0116] When the binder that covers or contacts the surface of the active material forms a film, it is called a passive film. It is expected that the passive film will also play a role in preventing the decomposition of the electrolyte. It is a film with no or very low electrical conductivity, for example, on the surface of an active material. When a dynamic membrane is formed, it is possible to suppress the decomposition of the electrolyte at the battery reaction potential. In addition, the passive film suppresses electrical conductivity while allowing lithium ions to conduct. And even more desirable.

[0117] <Positive electrode current collector> The positive electrode current collector may be made of metals such as stainless steel, gold, platinum, aluminum, titanium, or the like. In addition, the material used for the positive electrode current collector can be an alloy of these materials, which has high electrical conductivity. It is preferable that the material does not dissolve at the potential of the positive electrode. Aluminum alloys containing elements such as indium and molybdenum that improve heat resistance are used. It can also be formed from a metal element that reacts with silicon to form a silicide. Metal elements that react with silicon to form silicide include zirconium, titanium, and Tantalum, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten , cobalt, nickel, etc. Current collectors are available in foil, plate (sheet), mesh, punched The current collector may be in the form of a metal, an expanded metal, or the like. It is advisable to use one with a thickness of 5 μm or more and 30 μm or less.

[0118] [Negative electrode] The negative electrode has a negative electrode active material layer and a negative electrode current collector. The negative electrode active material layer contains a conductive assistant and and a binder.

[0119] <Negative electrode active material> As the negative electrode active material, for example, an alloy-based material or a carbon-based material can be used.

[0120] As a negative electrode active material, it is possible to carry out charge / discharge reactions by alloying / de-alloying reactions with lithium. For example, silicon, tin, gallium, aluminum, and Rumanium, lead, antimony, bismuth, silver, zinc, cadmium, indium, etc. Materials containing at least one of these elements can be used. These elements have a large capacity compared to carbon. Silicon has a high theoretical capacity of 4200mAh / g. It is preferable to use silicon. Compounds containing these elements may also be used. For example, SiO, Mg2Si, Mg2Ge, SnO, SnO2, Mg2Sn, SnS2, V 2Sn3, FeSn2, CoSn2, Ni3Sn2, Cu6Sn5, Ag3Sn, Ag3 Sb, Ni2MnSb, CeSb3, LaSn3, La3Co2Sn7, CoSb3, I nSb, SbSn, etc. Here, the charge / discharge reaction occurs due to alloying / dealloying reactions with lithium. Elements capable of undergoing a reaction and compounds containing such elements are sometimes called alloy materials. do.

[0121] In this specification, SiO refers to, for example, silicon monoxide. Alternatively, SiO x Here, it is preferable that x has a value close to 1. For example, x is 0 A value between 0.2 and 1.5 is preferred, and a value between 0.3 and 1.2 is more preferred.

[0122] Carbon-based materials include graphite, graphitizable carbon (soft carbon), and non-graphitizable carbon (hard carbon). Carbon nanotubes, graphene, carbon black, etc. may be used. .

[0123] Examples of graphite include artificial graphite and natural graphite. Examples of artificial graphite include mesophase graphite. Carbon microbeads (MCMB), coke-based artificial graphite, pitch-based artificial graphite, etc. Here, as the artificial graphite, spherical graphite having a spherical shape can be used. For example, the MCMB may have a spherical shape, which is preferred. It is relatively easy to reduce the particle size, which may be preferable. Examples of the graphite include flake graphite and spherical natural graphite.

[0124] When lithium ions are inserted into graphite (when lithium-graphite intercalation compounds are formed), It has a low potential similar to that of lithium metal (0.05V to 0.3V vs. Li / L i + This allows the lithium-ion secondary battery to exhibit a high operating voltage. In addition, graphite has a relatively high capacitance per unit volume, a relatively small volume expansion, and is inexpensive. However, lithium ions are preferred because they have the advantage of being safer than metallic lithium.

[0125] In addition, titanium dioxide (TiO2) and lithium titanium oxide (Li4T i5O 12 ), lithium-graphite intercalation compound (Li x C6), niobium pentoxide (Nb2O5) Oxides such as tungsten oxide (WO2) and molybdenum oxide (MoO2) can be used. can.

[0126] In addition, the negative electrode active material is a composite nitride of lithium and transition metals, which has a Li3N structure. Li 3-x M x N (M=Co, Ni, Cu) can be used. For example, Li 2.6 Co 0.4 N3 has a large charge / discharge capacity (900mAh / g, 1890mAh / cm 3 ) And preferable.

[0127] When a composite nitride of lithium and transition metals is used, the negative electrode active material contains lithium ions, The positive electrode active material is made of V2O5, Cr3O8, etc., which do not contain lithium ions. It is preferable that the positive electrode active material contains lithium ions. The lithium ions contained in the positive electrode active material are first removed to form the negative electrode active material. A complex nitride of lithium and a transition metal can be used.

[0128] In addition, a material that undergoes a conversion reaction can also be used as the negative electrode active material. For example, Lithium oxide (LiO), cobalt oxide (CoO), nickel oxide (NiO), iron oxide (FeO), etc. A transition metal oxide that does not form an alloy with the negative electrode active material may be used. Further materials that are produced include Fe2O3, CuO, Cu2O, RuO2, Cr2O3, etc. oxide, CoS 0.89 , NiS, CuS and other sulfides, Zn3N2, Cu3N, Ge3 Nitrides such as N4, phosphides such as NiP2, FeP2, CoP3, FeF3, BiF3, etc. It also occurs with fluoride.

[0129] The conductive assistant and binder that can be contained in the negative electrode active material layer are the same as those that can be contained in the positive electrode active material layer. The conductive additive and binder may be the same as those that can be used.

[0130] <Negative electrode current collector> The negative electrode current collector can be made of the same material as the positive electrode current collector. It is preferable to use a material that does not alloy with carrier ions such as lithium.

[0131] [Electrolyte] The electrolytic solution contains a solvent and an electrolyte. The solvent for the electrolytic solution is preferably an aprotic organic solvent. For example, ethylene carbonate (EC), propylene carbonate (PC), ethylene carbonate, chloroethylene carbonate, vinylene carbonate, gamma-butyrolactone lactone, γ-valerolactone, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, ethyl acetate ethyl propionate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, 1 ,3-dioxane, 1,4-dioxane, dimethoxyethane (DME), dimethylsulfur oxide, diethyl ether, methyl diglyme, acetonitrile, benzonitrile, tetrahydrofuran One of trihydrofuran, sulfolane, sultone, etc., or two or more of these Combinations and ratios may be used.

[0132] In addition, by using a polymer material that gels as a solvent for the electrolyte, safety against leakage, etc. is improved. The safety of the secondary battery is improved. In addition, the secondary battery can be made thinner and lighter. Representative examples of materials are silicone gel, acrylic gel, acrylonitrile gel, and polyethylene gel. Styrene oxide gel, polypropylene oxide gel, fluorine polymer gel, etc. There is.

[0133] In addition, a flame-retardant and non-volatile ionic liquid (room-temperature molten salt) is used as the solvent for the electrolyte. By using one or more batteries, the internal temperature of the storage device can be increased due to an internal short circuit or overcharging. Even if the battery is heated, it can prevent explosion or fire of the battery. Ionic liquids are made of cations and anions. The electrolyte solution contains an organic cation and an anion. Ammonium cations, tertiary sulfonium cations, and quaternary phosphonium cations, etc. Aliphatic onium cations such as imidazolium cations and pyridinium cations Aromatic cations are also used as anions in electrolytes. Anions, monovalent methide anions, fluorosulfonate anions, perfluoroalkyl Sulfonate anion, tetrafluoroborate anion, perfluoroalkylborate anion, hexafluorophosphate anion, or perfluoroalkyl phosphate anions, etc.

[0134] The electrolyte to be dissolved in the above solvent is, for example, LiPF6, LiClO4, Li AsF6, LiBF4, LiAlCl4, LiSCN, LiBr, LiI, Li2SO4 , Li2B 10 Cl 10 , Li2B 12 Cl 12 , LiCF3SO3, LiC4F9SO 3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiN(CF3SO2) 2. Lithium such as LiN(C4F9SO2)(CF3SO2) and LiN(C2F5SO2)2 Use one or more of these salts in any combination and ratio. can be done.

[0135] The electrolyte used in the electricity storage device is free of granular waste and elements other than the constituent elements of the electrolyte (hereinafter simply referred to as "inorganic It is preferable to use a highly purified electrolyte solution with a low content of ruthenium oxide (also called "pure substance"). Specifically, the weight ratio of impurities to the electrolyte is 1% or less, preferably 0.1% or less, more preferably It is preferably 0.01% or less.

[0136] In addition, vinylene carbonate, propane sultone (PS), and tert-butyl ether were used in the electrolyte. Benzene (TBB), Fluoroethylene Carbonate (FEC), LiBOB, and Squishi Dinitrile compounds such as diisopropylnitrile and adiponitrile may also be added. The concentration of may be, for example, 0.1 wt % or more and 5 wt % or less with respect to the entire solvent.

[0137] Alternatively, a polymer gel electrolyte may be used in which a polymer is swollen with an electrolytic solution. By using electrolytes, safety against leakage etc. is improved. It is possible to reduce the weight.

[0138] The polymers that can be gelled include silicone gel, acrylic gel, acrylonitrile gel, Polyethylene oxide gel, polypropylene oxide gel, fluorine-based polymer A gel or the like can be used.

[0139] Examples of the polymer include polyalkylene oxides such as polyethylene oxide (PEO). Polymers with a fluororesin structure, PVDF, polyacrylonitrile, etc., and their combinations For example, a copolymer containing PVDF and hexafluoropropylene (H PVDF-HFP, a copolymer of PVDF and PVDF, can be used. The mer may have a porous shape.

[0140] In addition, instead of the electrolyte, solid electrolytes containing inorganic materials such as sulfides and oxides, and P A solid electrolyte containing a polymer material such as EO (polyethylene oxide) can be used. When a solid electrolyte is used, the installation of a separator or spacer becomes unnecessary. Since the entire pond can be solidified, there is no risk of leakage, and safety is improved dramatically.

[0141] [Separator] The secondary battery preferably has a separator. The separator may be, for example, a paper. Cellulose-containing fibers, nonwoven fabrics, glass fibers, ceramics, or nanofibers, including those containing cellulose, IRON (polyamide), VINYLON (polyvinyl alcohol fiber), polyester, acrylic The material used must be synthetic fibers such as olefin, polyolefin, and polyurethane. The separator is processed into a bag shape and placed so that it encases either the positive electrode or the negative electrode. It is preferable to do so.

[0142] The separator may have a multi-layer structure. For example, the separator may be made of an organic material such as polypropylene or polyethylene. The material film is made of ceramic, fluorine, polyamide, or a combination of these. The ceramic material can be, for example, arsenic oxide. Aluminum particles, silicon oxide particles, etc. can be used. For example, PVDF, polytetrafluoroethylene, etc. can be used. Polyamide-based materials Examples of materials used include nylon and aramid (meta-aramid and para-aramid). It is possible.

[0143] Coating with ceramic materials improves oxidation resistance, making it ideal for separators during high-voltage charging and discharging. This suppresses the deterioration of the capacitor and improves the reliability of the secondary battery. By coating the electrode, the separator and the electrode are more easily adhered to each other, improving the output characteristics. Coating polyamide materials, especially aramid, improves heat resistance, which contributes to the safety of secondary batteries. This can improve safety.

[0144] For example, a mixture of aluminum oxide and aramid is coated on both sides of a polypropylene film. Alternatively, the surface of the polypropylene film that comes into contact with the positive electrode may be coated with aluminum oxide. Alternatively, the surface in contact with the negative electrode may be coated with a mixed material of rubber and aramid, and a fluorine-based material may be coated on the surface. .

[0145] By using a multi-layered separator, the safety of the secondary battery can be ensured even if the overall thickness of the separator is thin. Since the capacity per unit volume of the secondary battery can be increased, the capacity per unit volume of the secondary battery can be increased.

[0146] (Embodiment 3) In this embodiment, the shape of a secondary battery having the positive electrode active material 100 described in the previous embodiment is The material used in the secondary battery described in this embodiment is the same as that in the previous embodiment. The description of the form may be taken into consideration.

[0147] [Coin-type secondary battery] First, an example of a coin-type secondary battery will be described. Figure 4(A) shows a coin-type (single-layer flat type) FIG. 4(B) is a cross-sectional view of the secondary battery.

[0148] The coin-type secondary battery 300 has a positive electrode can 301 that also serves as a positive electrode terminal and a negative electrode can 302 that also serves as a negative electrode terminal. 302 is insulated and sealed by a gasket 303 made of polypropylene or the like. The positive electrode 304 is composed of a positive electrode current collector 305 and a positive electrode active material layer 306 provided in contact with the positive electrode current collector 305. The negative electrode 307 is formed by contacting a negative electrode current collector 308. The negative electrode active material layer 309 is formed by bonding the negative electrode active material layer 309 to the negative electrode.

[0149] The positive electrode 304 and the negative electrode 307 used in the coin-type secondary battery 300 are each an active material. The barrier layer need only be formed on one side.

[0150] The positive electrode can 301 and the negative electrode can 302 are made of nickel or aluminum, which is resistant to corrosion by the electrolyte. , titanium, or alloys of these with other metals (e.g. stainless steel In addition, nickel or aluminum can be used to prevent corrosion by the electrolyte. The positive electrode can 301 is for covering the positive electrode 304, and the negative electrode can 302 is for covering the negative electrode 304. 7 and electrically connected to each other.

[0151] The negative electrode 307, the positive electrode 304 and the separator 310 are impregnated with an electrolyte, as shown in FIG. As shown in FIG. 1, the positive electrode can 301 is placed downward, the positive electrode 304, the separator 310, the negative electrode 307, and the negative The positive electrode can 301 and the negative electrode can 302 are laminated in this order, and the positive electrode can 301 and the negative electrode can 302 are fixed with a gasket 303 interposed therebetween. Then, the laminate is pressed to manufacture a coin-type secondary battery 300.

[0152] By using the positive electrode active material described in the above embodiment for the positive electrode 304, it is possible to achieve high capacity and cycle. The coin-type secondary battery 300 can be made to have excellent characteristics.

[0153] [Cylindrical secondary battery] Next, an example of a cylindrical secondary battery will be described with reference to FIG. As shown in FIG. 5(A), the battery has a positive electrode cap (battery cover) 601 on the top surface and The battery can (external can) 602 is disposed on the bottom surface. It is insulated from 02 by a gasket (insulating packing) 610.

[0154] Fig. 5(B) is a schematic diagram showing a cross section of a cylindrical secondary battery. On the inside of 602, a strip-shaped positive electrode 604 and a negative electrode 606 are wound with a separator 605 sandwiched between them. Although not shown, the battery element is wound around a center pin. The battery can 602 is closed at one end and open at the other end. Metals such as nickel, aluminum, titanium, etc., which are resistant to corrosion by the electrolyte, or Alloys of these and other metals (eg, stainless steel, etc.) can be used. In order to prevent corrosion by the electrolyte, it is preferable to coat the material with nickel, aluminum, or the like. The battery element, in which the positive electrode, the negative electrode, and the separator are wound, is The battery is sandwiched between a pair of opposing insulating plates 608 and 609. The inside of the battery can 602 is filled with a non-aqueous electrolyte (not shown). The same as the in-type secondary battery can be used.

[0155] The positive and negative electrodes used in cylindrical secondary batteries are wound, so active material is formed on both sides of the current collector. A positive electrode terminal (positive electrode current collecting lead) 603 is connected to the positive electrode 604, and a negative A negative electrode terminal (negative electrode current collecting lead) 607 is connected to the positive electrode 606. The positive terminal 607 may be made of a metal material such as aluminum. 03 is resistance welded to the safety valve mechanism 612, and the negative terminal 607 is resistance welded to the bottom of the battery can 602. The safety valve mechanism 612 is a PTC (Positive Temperature Coefficient) The positive electrode cap 601 is electrically connected to the positive electrode cap 601 via a capacitance 611. The safety valve mechanism 612 is a mechanism for releasing the positive electrode cap 601 when the internal pressure of the battery increases beyond a predetermined threshold. The PTC element 611 cuts off the electrical connection between the positive electrode 604 and the positive electrode 604. It is a thermal resistor element whose resistance increases when the temperature rises, and the amount of current is limited by the increase in resistance. It prevents abnormal heat generation. The PTC element is made of barium titanate (BaTiO3) Semiconductor ceramics and the like can be used.

[0156] 5C, a plurality of secondary batteries 600 are arranged between conductive plates 613 and 614. A module 615 may be formed by sandwiching the secondary batteries 600 between them. Alternatively, the elements may be connected in series, or may be connected in parallel and then in series. By configuring a module 615 having a plurality of secondary batteries 600, This allows for the extraction of large amounts of power.

[0157] FIG. 5D is a top view of the module 615. The conductive plate 613 is dotted for clarity. As shown in FIG. 5D, the module 615 is a multiple secondary battery 600. The conductive plate 613 may be provided on the conductive wire 616. In addition, even if a temperature control device 617 is provided between multiple secondary batteries 600, When the secondary battery 600 is overheated, the temperature control device 617 cools the secondary battery. If 600 is too cold, it can be heated by the temperature control device 617. Therefore, the performance of the module 615 is less affected by the outside temperature.

[0158] By using the positive electrode active material 100 described in the previous embodiment for the positive electrode 604, a high capacity and low-temperature battery can be obtained. This results in a cylindrical secondary battery 600 with excellent cycling characteristics.

[0159] [Example of secondary battery structure] Another structural example of the secondary battery will be described with reference to FIGS.

[0160] 6(A) and 6(B) are diagrams showing the external appearance of a battery pack. The battery pack includes a circuit The secondary battery 913 includes a terminal 951 and a terminal 52 and is covered with a label 910. The battery pack also has an antenna 914. Good too.

[0161] The circuit board 900 is fixed with a seal 915. The circuit board 900 has a circuit 912. The terminal 911 is connected to a terminal 951 of the secondary battery 913 and a terminal 952 of the secondary battery 913 via the circuit board 900. The terminal 911 is electrically connected to the antenna via the circuit board 900. The terminals 911 are electrically connected to the power supply 914 and the circuit 912. Each of the terminals 911 may be a control signal input terminal, a power supply terminal, or the like.

[0162] The circuit 912 is, for example, a protection circuit for protecting the secondary battery 913 from overcharging, over-discharging, and overcurrent. The circuit 912 may be provided on the back surface of the circuit board 900. The antenna 914 is not limited to a coil shape, and may be, for example, a wire shape or a plate shape. In addition, flat antennas, aperture antennas, traveling wave antennas, EH antennas, magnetic field antennas, etc. Alternatively, an antenna such as a dielectric antenna may be used. The battery pack and the battery pack via the antenna 914 can communicate with each other. As a communication method with other devices, NFC, etc., is used between the battery pack and other devices. It is possible to apply a response method that allows

[0163] The battery pack has a layer 916 between the antenna 914 and the secondary battery 913. The layer 916 has a function of blocking an electromagnetic field generated by, for example, the secondary battery 913. For example, a magnetic material can be used as the material.

[0164] The structure of the battery pack is not limited to that shown in FIG.

[0165] For example, as shown in Figs. 7(A-1) and 7(A-2), An antenna 918 may be provided on the other pair of opposing surfaces of the secondary battery 913 shown in FIG. FIG. 7(A-1) is an external view seen from one side of the pair of faces, and FIG. 7(A-2) is an external view seen from one side of the pair of faces. 6(A) and 6(B) are external views seen from the other side of the pair of surfaces. The same parts as those of the battery pack are described in the battery pack explanations shown in Figs. 6(A) and 6(B). can be used as appropriate.

[0166] As shown in FIG. 7(A-1), a layer 916 is sandwiched between one of a pair of surfaces of a secondary battery 913 to form an annular 7(A-2), a retainer 914 is provided on the other of the pair of surfaces of the secondary battery 913. An antenna 918 is provided on the second layer 913, with a layer 917 sandwiched therebetween. The layer 917 has a function of blocking electromagnetic fields caused by the electromagnetic waves. There can be.

[0167] By adopting the above structure, two antennas are provided in the battery pack, and the antennas 914 and The size of both antennas 918 can be increased.

[0168] The antenna 918 can be of a shape that can be applied to the antenna 914. Furthermore, the antenna 918 may be a flat conductor. This flat conductor may be a conductor for electric field coupling. In other words, the capacitor has two conductors. The antenna 914 may function as a single conductor. This allows only electromagnetic and magnetic fields to be detected. Alternatively, power can be exchanged using an electric field.

[0169] Or, as shown in FIG. 7(B-1), the battery pack shown in FIG. 6(A) and FIG. 6(B) may be A display device 920 may be provided. The display device 920 is electrically connected to the terminal 911. 6(A) and 6(B), the same parts as those of the battery pack shown in FIG. The description of the battery pack shown in 6(B) can be used as appropriate.

[0170] The display device 920 displays, for example, an image indicating whether charging is in progress, an image indicating the amount of stored power, etc. The display device 920 may be, for example, an electronic paper, a liquid crystal display device, an electrophotographic display device, or the like. For example, an electroluminescence (EL) display device can be used. By using the par, the power consumption of the display device 920 can be reduced.

[0171] Alternatively, as shown in FIG. 7(B-2), the secondary battery 913 shown in FIG. 6(A) and FIG. 6(B) A sensor 921 may be provided. The sensor 921 is connected to a terminal 922 and a circuit board 900. 6A and 6B. For the same parts, the description of the power storage device shown in FIG. 6(A) and FIG. 6(B) can be appropriately used. .

[0172] The sensor 921 may be, for example, a sensor for detecting displacement, position, speed, acceleration, angular velocity, number of rotations, distance, light, etc. , liquid, magnetic, temperature, chemical, sound, time, hardness, electric field, current, voltage, power, radiation, flow It is sufficient if the device has the function of measuring the amount, humidity, gradient, vibration, odor, or infrared rays. By providing the sensor 921, for example, data indicating the environment in which the power storage device is placed can be obtained. It is also possible to detect a signal (such as temperature) and store it in memory within the circuit 912.

[0173] Further, a structural example of the secondary battery 913 will be described with reference to FIGS.

[0174] A secondary battery 913 shown in FIG. 8A is provided with a terminal 951 and a terminal 952 inside a housing 930. The winding body 950 is impregnated with an electrolyte inside the housing 930. The terminal 952 is in contact with the housing 930, and the terminal 951 is in contact with the housing by using an insulating material or the like. 8A, the housing 930 is not in contact with the housing 930. However, in reality, the winding body 950 is covered by the housing 930, and the terminals 951 and 952 are The housing 930 is made of a metal material (e.g., aluminum). etc.) or resin materials can be used.

[0175] As shown in FIG. 8B, the housing 930 shown in FIG. 8A is formed from a plurality of materials. For example, the secondary battery 913 shown in FIG. 8B may be divided into a housing 930a and a housing 930b. The wound body 950 is disposed in the area surrounded by the housing 930a and the housing 930b. It is provided.

[0176] The housing 930a can be made of an insulating material such as an organic resin. By using a material such as organic resin on the surface on which the secondary battery 913 is formed, If the shielding of the electric field by the housing 930a is small, the shielding of the housing 930a can be suppressed. Antennas such as antenna 914 and antenna 918 may be provided inside the housing 930b. For example, a metal material can be used.

[0177] The structure of the wound body 950 is shown in FIG. The winding body 950 has a separator 933 sandwiched therebetween. A negative electrode 931 and a positive electrode 932 are stacked on top of each other, and the laminated sheet is wound to form a wound body. In addition, the negative electrode 931, the positive electrode 932, and the separator 933 may be laminated in a plurality of layers. May be layered.

[0178] The negative electrode 931 is connected to the terminal 911 shown in FIG. 6 via one of the terminals 951 and 952. The positive electrode 932 is connected to the terminal 911 shown in FIG. Connected.

[0179] By using the positive electrode active material described in the above embodiment for the positive electrode 932, the battery can be cycled with a high capacity. The secondary battery 913 can have excellent characteristics.

[0180] [Laminated secondary battery] Next, an example of a laminated secondary battery will be described with reference to FIGS. If the laminated secondary battery is made flexible, the flexible portion is at least If the secondary battery is mounted on an electronic device that also has a battery, the secondary battery can be bent according to the deformation of the electronic device. can.

[0181] A laminated secondary battery 980 will be described with reference to FIG. The battery 980 has a wound body 993 shown in FIG. 9, a positive electrode 995, and a separator 996. The wound body 993 is the same as the wound body 991 described in FIG. As with the case 950, a negative electrode 994 and a positive electrode 995 are overlapped with a separator 996 interposed therebetween. The laminated sheet is then wound.

[0182] The number of layers of the negative electrode 994, the positive electrode 995, and the separator 996 is determined as required. The negative electrode 994 is connected to the lead electrode 997 and the lead The positive electrode 995 is connected to a negative electrode collector (not shown) via one of the lead electrodes 998. The other of the electrode 997 and the lead electrode 998 is connected to a positive electrode current collector (not shown).

[0183] As shown in FIG. 10B, a film 981 that serves as an exterior body and a film 98 having a recess are 2 are bonded together by thermocompression or the like to form a space in which the above-mentioned wound body 993 is housed. In this way, a secondary battery 980 can be manufactured as shown in FIG. 3 has a lead electrode 997 and a lead electrode 998, a film 981, and a recess The inside of the film 982 is impregnated with an electrolyte.

[0184] The film 981 and the film 982 having the recesses are made of a metal material such as aluminum. The film 981 and the film 982 having the recesses can be made of a resin material. If a resin material is used as the material, when an external force is applied, the film 981 and the recessed portion The film 982 having the electrode can be deformed to produce a secondary battery having flexibility. can be done.

[0185] In addition, although Fig. 10(B) and Fig. 10(C) show an example in which two films are used, A space is formed by folding one sheet of film, and the above-mentioned wound body 99 is inserted into the space. It may also accommodate 3.

[0186] By using the positive electrode active material described in the previous embodiment for the positive electrode 995, it is possible to achieve high capacity cycling. The secondary battery 980 can have excellent characteristics.

[0187] In addition, in FIG. 10, a secondary battery 9 having a wound body in a space formed by a film that serves as an exterior body is shown. We have explained the example of 80, but as shown in Figure 11, the shape is determined by the film that is the exterior body. The space defined by the positive electrode layer can be used as a secondary battery having a plurality of rectangular positive electrodes, separators, and negative electrodes. good.

[0188] The laminated secondary battery 500 shown in FIG. 11(A) includes a positive electrode current collector 501 and a positive electrode active material. A positive electrode 503 having a positive electrode active material layer 502, a negative electrode current collector 504 and a negative electrode active material layer 505. The battery includes a negative electrode 506, a separator 507, an electrolyte 508, and an exterior body 509. A separator 507 is provided between a positive electrode 503 and a negative electrode 506 provided in a body 509. The exterior body 509 is filled with an electrolyte 508. The electrolyte solution shown in the second embodiment can be used.

[0189] In the laminated secondary battery 500 shown in FIG. 11(A), a positive electrode current collector 501 and a negative electrode current collector The positive electrode current collector 504 also serves as a terminal for obtaining electrical contact with the outside. A part of the current collector 501 and the negative electrode current collector 504 is exposed to the outside from the exterior body 509. In addition, the positive electrode current collector 501 and the negative electrode current collector 504 may be arranged in a manner similar to that described above. Instead of exposing it to the outside, a lead electrode is used to connect the lead electrode to the positive electrode current collector 501 or the negative electrode The lead electrode may be exposed to the outside by ultrasonic bonding to the current collector 504 .

[0190] In the laminated secondary battery 500, the exterior body 509 is made of, for example, polyethylene, poly A film made of propylene, polycarbonate, ionomer, polyamide, etc. is coated with a A thin metal film with excellent flexibility, such as aluminum, stainless steel, copper, or nickel, is applied. On the metallic thin film, an insulating synthetic resin such as polyamide resin or polyester resin is applied as the outer surface of the exterior body. A laminate film having a three-layer structure with an oil film can be used.

[0191] An example of the cross-sectional structure of a laminated secondary battery 500 is shown in FIG. For simplicity, A) shows an example consisting of two current collectors, but in reality, it is composed of multiple electrode layers. It consists of:

[0192] In FIG. 11B, as an example, the number of electrode layers is 16. In FIG. 11B, the negative electrode current collector 504 has eight layers. The positive electrode current collector 501 has a structure of 8 layers, totaling 16 layers. The cross section of the extraction part is shown, and eight layers of negative electrode current collector 504 are ultrasonically bonded. The number of electrode layers is not limited to 16, and may be more or less. In addition, when the number of electrode layers is small, the secondary battery can have a larger capacity. In this case, a secondary battery can be made thin and has excellent flexibility.

[0193] An example of the external appearance of a laminated secondary battery 500 is shown in FIGS. 12 and 13. 2 and 13 show a positive electrode 503, a negative electrode 506, a separator 507, an outer casing 509, a positive electrode lead The positive electrode 510 and the negative electrode 511 are connected to each other.

[0194] FIG. 14A shows an external view of a positive electrode 503 and a negative electrode 506. The positive electrode 503 is connected to a positive electrode current collector 50 1, and the positive electrode active material layer 502 is formed on the surface of the positive electrode current collector 501. 503 has a region where the positive electrode current collector 501 is partially exposed (hereinafter referred to as a tab region). 506 has a negative electrode current collector 504, and a negative electrode active material layer 505 is formed on the surface of the negative electrode current collector 504. In addition, the negative electrode 506 has a region where the negative electrode current collector 504 is partially exposed, that is, a tab region. The area and shape of the tab regions of the positive electrode and the negative electrode are not limited to the example shown in FIG. I can't.

[0195] [Method of manufacturing laminated secondary battery] Here, an example of a method for producing a laminated secondary battery shown in FIG. 12 will be described with reference to FIG. This will be explained using (B) and (C).

[0196] First, the negative electrode 506, the separator 507, and the positive electrode 503 are laminated. The negative electrode 506, the separator 507, and the positive electrode 503 are shown. Next, the bonding of the tab regions of the positive electrode 503 and the bonding of the tabs of the positive electrode on the outermost surface are shown. The positive electrode lead electrode 510 is bonded to the region. For example, ultrasonic welding or the like may be used for bonding. Similarly, the bonding between the tab regions of the negative electrodes 506 and the bonding of the negative electrode leads to the tab region of the outermost negative electrode are preferably performed. Then, the metal layer 511 is bonded.

[0197] Next, the negative electrode 506 , the separator 507 and the positive electrode 503 are placed on the exterior body 509 .

[0198] Next, as shown in FIG. 14(C), the exterior body 509 is folded at the portion indicated by the dashed line. After that, the outer periphery of the exterior body 509 is bonded. For example, thermocompression bonding may be used for bonding. 509, so that the electrolyte 508 can be poured in later. An area that is not joined (hereinafter referred to as an inlet) is provided.

[0199] Next, the electrolyte 508 is introduced into the inside of the exterior body 509 through an inlet provided in the exterior body 509. The electrolyte 508 is preferably introduced under a reduced pressure or an inert gas atmosphere. Finally, the inlet is joined. In this way, a laminated secondary battery is produced. A secondary battery 500 can be fabricated.

[0200] By using the positive electrode active material described in the above embodiment for the positive electrode 503, it is possible to achieve high capacity and cycle. The secondary battery 500 can have excellent characteristics.

[0201] [Bendable secondary battery] Next, an example of a bendable secondary battery will be described with reference to FIGS. 15 and 16. .

[0202] FIG. 15(A) shows a schematic top view of a bendable battery 250. (B2) and (C) are cut along the lines C1-C2 and C3-C4 in FIG. 15(A), respectively. 2 is a schematic cross-sectional view taken along the line A1-A2. The positive electrode 211a and the negative electrode 211b are housed inside the battery 251. A lead 212a electrically connected to the negative electrode 211b and a lead 21 2b extends outside the exterior body 251. In addition, in the area surrounded by the exterior body 251, In addition to the electrode 211a and the negative electrode 211b, an electrolyte (not shown) is enclosed.

[0203] The positive electrode 211a and the negative electrode 211b of the battery 250 will be described with reference to FIG. FIG. 16(A) illustrates the stacking order of the positive electrode 211a, the negative electrode 211b, and the separator 214. FIG. 16(B) shows a perspective view of the positive electrode 211a and the negative electrode 211b, as well as a lead 2 12a and a lead 212b.

[0204] As shown in FIG. 16A, the battery 250 includes a plurality of rectangular positive electrodes 211a, a plurality of rectangular The positive electrode 211a and the negative electrode 211b are connected to the positive electrode 211a and the negative electrode 211b. Each of the positive electrodes 211a and 211b has a protruding tab portion and a portion other than the tab. A positive electrode active material layer is formed on the portion other than the tab, and the negative electrode 211b is formed on the portion other than the tab on one surface of the negative electrode 211b. A negative electrode active material layer is formed.

[0205] The surfaces of the positive electrode 211a on which the positive electrode active material layer is not formed and the surfaces of the negative electrode 211b on which the negative electrode active material layer is not formed are The positive electrode 211a and the negative electrode 211b are laminated so that the surfaces without the layer are in contact with each other. can be.

[0206] In addition, the surface of the positive electrode 211a on which the positive electrode active material is formed and the surface of the negative electrode 211b on which the negative electrode active material is formed are A separator 214 is provided between the two surfaces. The regulator 214 is shown in dotted line.

[0207] As shown in FIG. 16B, the positive electrodes 211a and the leads 212a are connected to each other at the joints 215. The negative electrodes 211b and the leads 212b are electrically connected to each other at the joints 211a. Electrical connection is made at 15b.

[0208] Next, the exterior body 251 will be described with reference to FIGS. 15(B1), (B2), (C), and (D). do.

[0209] The exterior body 251 has a film-like shape and is arranged to sandwich the positive electrode 211a and the negative electrode 211b. The exterior body 251 is folded in two at the folded portion 261 and a pair of seal portions 2 The pair of sealing parts 262 are connected to the positive electrode 211a and the negative electrode 211b. The seal portion 26 is provided on either side of the electrode 211b and can also be called a side seal. 3 has a portion overlapping with the lead 212a and the lead 212b, and is also called a top seal. This can be done.

[0210] The exterior body 251 has a ridge line 271 and a valley line 272 at the portion overlapping the positive electrode 211a and the negative electrode 211b. It is preferable that the sealing portion 26 of the exterior body 251 has a corrugated shape in which the grooves 72 are arranged alternately. 2 and the seal portion 263 are preferably flat.

[0211] FIG. 15(B1) is a cross section cut at the portion overlapping with the ridge line 271, and FIG. 15(B2) is a cross section cut at the portion overlapping with the ridge line 271. The cross section is taken at the part overlapping with the valley line 272. 250 and 251 correspond to cross sections in the width direction of the positive electrode 211a and the negative electrode 211b.

[0212] Here, the distance between the end of the negative electrode 211b in the width direction and the seal portion 262 is defined as La. When the battery 250 is deformed, for example by bending, the positive electrode 211a and the negative electrode In this case, if the distance La is too short, the outer The exterior body 251 rubs strongly against the positive electrode 211a and the negative electrode 211b, and the exterior body 251 is damaged. In particular, if the metal film of the exterior body 251 is exposed, the metal film may become electrically Therefore, it is recommended to set the distance La as long as possible. On the other hand, if the distance La is too large, the volume of the battery 250 increases. Put away.

[0213] In addition, the greater the total thickness of the laminated positive electrode 211a and negative electrode 211b, the greater the It is preferable to increase the distance La between b and the seal portion 262 .

[0214] More specifically, the laminated positive electrode 211a and negative electrode 211b and a separator (not shown) are When the total thickness of the data input 214 is thickness t, the distance La is 0.8 times or more and 3.0 times or less of thickness t. times or less, preferably 0.9 times or more and 2.5 times or less, more preferably 1.0 times or more and 2.0 times or less. By setting the distance La in this range, the device can be compact and resistant to bending. This makes it possible to realize a highly reliable battery.

[0215] In addition, when the distance between the pair of seal portions 262 is a distance Lb, the distance Lb is It is preferable that the width of the battery 250 is sufficiently larger than the width Wb of the battery 250. When the positive electrode 211a and the negative electrode 211b are deformed, the positive electrode 211a and the negative electrode 211b come into contact with the exterior body 251. Even if the positive electrode 211a and the negative electrode 211b are in contact with each other, a part of the positive electrode 211a and the negative electrode 211b can be shifted in the width direction. To effectively prevent the electrode 211a and the negative electrode 211b from rubbing against the exterior body 251. can be done.

[0216] For example, the difference between the distance Lb between the pair of seal portions 262 and the width Wb of the negative electrode 211b is 1.6 times or more and 6.0 times or less, preferably 1.8 times, the thickness t of the negative electrode 211a and the negative electrode 211b It is preferable that the ratio is 2.0 to 4.0 times. .

[0217] In other words, it is preferable that the distance Lb, the width Wb, and the thickness t satisfy the relationship of the following formula 1. It is.

[0218]

number

[0219] Here, a is 0.8 or more and 3.0 or less, preferably 0.9 or more and 2.5 or less, and more preferably is greater than or equal to 1.0 and less than or equal to 2.0.

[0220] FIG. 15(C) is a cross section including the lead 212a, and shows the battery 250, the positive electrode 211a and As shown in FIG. 15(C), the bent portion 2 corresponds to a cross section of the negative electrode 211b in the longitudinal direction. In 61, the ends of the positive electrode 211a and the negative electrode 211b in the longitudinal direction and the exterior body 251 are It is preferable to have a space 273 therebetween.

[0221] FIG. 15(D) shows a schematic cross-sectional view of the battery 250 when bent. This corresponds to the cross section taken along line B1-B2 in FIG.

[0222] When the battery 250 is bent, the part of the exterior body 251 located on the outside of the bend stretches, and the part located on the inside More specifically, the part located on the outside of the exterior body 251 is deformed so as to shrink. The outer casing 251 deforms so that the amplitude of the wave becomes smaller and the period of the wave becomes larger. The part located inside the ridge deforms so that the wave amplitude is large and the wave period is small. In this way, the deformation of the exterior body 251 reduces the load applied to the exterior body 251 due to bending. Since the stress is relieved, the material that constitutes the exterior body 251 does not need to expand or contract. As a result, the battery 250 can be bent with a small force without damaging the exterior body 251.

[0223] Furthermore, as shown in FIG. 15(D), when the battery 250 is bent, the positive electrode 211a and the negative electrode 21 At this time, the stacked positive electrodes 211a and negative electrodes 211b are shifted relative to each other. Since one end of 211b on the side of the seal portion 263 is fixed by the fixing member 217, The amount of deviation increases toward the positive electrode 21. The stress applied to the positive electrode 211a and the negative electrode 211b is relieved, and the positive electrode 211a and the negative electrode 211b themselves As a result, the positive electrode 211a and the negative electrode 211b do not need to expand and contract. The battery 250 can be bent.

[0224] In addition, a space 273 is provided between the ends of the positive electrode 211a and the negative electrode 211b and the exterior body 251. As a result, when the electrode is bent, the ends of the positive electrode 211a and the negative electrode 211b located on the inside are However, the electrode 252 can be relatively displaced without coming into contact with the exterior body 251.

[0225] The battery 250 illustrated in FIG. 15 and FIG. 16 has a casing that retains its shape even after repeated bending and straightening. The positive electrode 211a and the negative electrode 211b are unlikely to break, and the battery characteristics are unlikely to deteriorate. The positive electrode 211a of the battery 250 is made of the positive electrode active material described in the previous embodiment. By using this material, it is possible to produce a battery with higher capacity and better cycle characteristics.

[0226] (Embodiment 4) In this embodiment, an example in which a secondary battery according to one embodiment of the present invention is mounted on an electronic device will be described. do.

[0227] First, as described in part of the third embodiment, a bendable secondary battery is mounted on an electronic device. An example is shown in Figure 17. An example of an electronic device that uses a bendable secondary battery is a tape. Revision equipment (also called television or television receiver), computer models, etc. Digital cameras, digital video cameras, digital photo frames, mobile phones ( Mobile phones, also called mobile phone devices, portable game machines, portable information terminals, audio playback devices, Examples include large game machines such as dick machines.

[0228] In addition, the flexible secondary battery can be mounted on the inner or outer walls of houses or buildings, or on the inside or outside of automobiles. It is also possible to incorporate it along the curved surfaces of the interior or exterior of the vehicle.

[0229] FIG. 17A shows an example of a mobile phone. A mobile phone 7400 includes a housing 7401. In addition to the display unit 7402, operation buttons 7403, an external connection port 7404, The mobile phone 7400 is equipped with a speaker 7405, a microphone 7406, etc. The secondary battery 7407 is a secondary battery of one embodiment of the present invention. This makes it possible to provide a lightweight mobile phone with a long life.

[0230] FIG. 17B shows the mobile phone 7400 in a curved state. When the battery is deformed by applying an external force to the battery, the secondary battery installed inside the battery is released. The secondary battery 7407 is also bent. At this time, the state of the bent secondary battery 7407 is shown in FIG. The secondary battery 7407 is a thin storage battery. The secondary battery 7407 is in a bent state. The secondary battery 7407 is fixed in place by a resistor. The semiconductor laser 7402 has a gate electrode 7408.

[0231] FIG. 17D shows an example of a bangle-type display device. The portable display device 7100 is The device includes a housing 7101 , a display unit 7102 , operation buttons 7103 , and a secondary battery 7104 . FIG. 17E shows the bent state of the secondary battery 7104. When the device is attached to the user's arm, the housing may deform and cause damage to part of the secondary battery 7104 or The total curvature changes. Note that the degree of curvature at any point on the curve is expressed as the radius of the corresponding circle. The value expressed is the radius of curvature, and the inverse of the radius of curvature is called the curvature. Within the range of 40 mm to 150 mm, a part of the main surface of the case or the secondary battery 7104 The radius of curvature of the main surface of the secondary battery 7104 is 40 mm or more and 150 mm or less. If the thickness is within the range of 1 mm or less, high reliability can be maintained. By using the secondary battery of one embodiment, a lightweight, long-life portable display device can be provided.

[0232] FIG. 17F shows an example of a wristwatch-type portable information terminal. The portable information terminal 7200 is , a housing 7201, a display unit 7202, a band 7203, a buckle 7204, and an operation button 72 05, input / output terminal 7206, etc.

[0233] The portable information terminal 7200 is capable of carrying out mobile telephone calls, e-mails, viewing and creating documents, playing music, and using the Internet. - It can run various applications such as internet communication and computer games. do.

[0234] The display unit 7202 has a curved display surface, and displays images along the curved display surface. The display portion 7202 is provided with a touch sensor, and can be used to input a touch signal to the screen using a finger or a stylus. For example, the icon 72 displayed on the display unit 7202 can be operated by touching it. You can launch the application by touching 07.

[0235] The operation button 7205 is used to set the time, turn the power on and off, and turn wireless communication on and off. It has various functions such as operation, silent mode activation and deactivation, power saving mode activation and deactivation, etc. For example, an operating system installed in the portable information terminal 7200 can The function of the operation button 7205 can also be freely set using the stem.

[0236] In addition, the mobile information terminal 7200 is capable of performing short-distance wireless communication according to a communication standard. For example, by communicating with a wireless headset, You can also make calls.

[0237] The portable information terminal 7200 also includes an input / output terminal 7206, and a connector for connecting to other information terminals. Data can be exchanged directly through the input / output terminal 7206. The charging operation can be performed by wireless power supply without going through the input / output terminal 7206. This is also possible.

[0238] A display portion 7202 of a portable information terminal 7200 includes a secondary battery of one embodiment of the present invention. By using the secondary battery of one embodiment of the present invention, a lightweight portable information terminal with a long life can be provided. For example, the secondary battery 7104 shown in FIG. 17E is curved inside the housing 7201. or may be incorporated in a bendable state inside the band 7203.

[0239] The portable information terminal 7200 preferably has a sensor. For example, a fingerprint sensor may be used as the sensor. Sensors for human body such as pulse sensors, body temperature sensors, touch sensors, pressure sensors, acceleration sensors It is preferable that the above-mentioned components are mounted on the vehicle.

[0240] FIG. 17G shows an example of a wristband-type display device. The display device 7300 includes a display unit 7 The display device 7300 includes a display 304 and a secondary battery of one embodiment of the present invention. The display unit 7304 may be equipped with a touch sensor, and may function as a portable information terminal. It is also possible.

[0241] The display surface of the display unit 7304 is curved, and the display can be performed along the curved display surface. In addition, the display device 7300 can display a display state by short-distance wireless communication according to a communication standard. The situation can be changed.

[0242] The display device 7300 also has an input / output terminal, and can directly connect to other information terminals via a connector. It is also possible to charge the device via the input / output terminals. The charging operation may be performed by wireless power supply without going through the input / output terminals.

[0243] By using the secondary battery of one embodiment of the present invention as the secondary battery included in the display device 7300, It is possible to provide a display device with a long life and low cost.

[0244] Next, FIG. 18(A) and FIG. 18(B) show an example of a foldable tablet terminal. The tablet terminal 9600 shown in FIG. 18(A) and FIG. 18(B) includes a housing 9630. a, housing 9630b, a movable part 9640 connecting the housing 9630a and the housing 9630b, Part 9631, display mode changeover switch 9626, power switch 9627, power saving mode The display has a mode changeover switch 9625, a fastener 9629, and an operation switch 9628. The display unit 9631 can be made of a flexible panel, making it possible to produce a tablet with a wider display area. FIG. 18A shows a tablet terminal 9600 in an open state. 18(B) shows the tablet terminal 9600 in a closed state.

[0245] The tablet terminal 9600 also includes a battery storage device inside the housing 9630a and the housing 9630b. The power storage unit 9635 is connected to the housing 9630a through the movable portion 9640. It is located across 9630b.

[0246] A part of the display unit 9631 can be used as a touch panel area, and the user can operate the displayed operation keys. You can enter data by touching the screen. You can also switch the keyboard display on the touch panel. By touching the area where the replacement button is displayed with your finger or a stylus, the display 9631 Keyboard buttons can be displayed.

[0247] A display mode changeover switch 9626 is used to change the display orientation between portrait and landscape. You can switch between black and white and color display. The touch 9625 detects when in use by an optical sensor built into the tablet terminal 9600. The brightness of the display can be optimized according to the amount of external light. In addition to optical sensors, other sensors such as gyros and acceleration sensors that detect tilt are also available. The device may be built-in.

[0248] FIG. 18B shows the tablet terminal in a closed state. The tablet terminal includes a housing 9630 and a solar cell 96 33, a charge / discharge control circuit 9634 including a DCDC converter 9636. A secondary battery according to one embodiment of the present invention is used as 9635.

[0249] In addition, since the tablet terminal 9600 can be folded in two, when not in use, the housing 9630a and The housing 9630b can be folded so that the housing 9630a and the housing 9630b overlap each other. Since the display portion 9631 can be protected, the durability of the tablet terminal 9600 can be improved. In addition, the power storage unit 9635 using the secondary battery of one embodiment of the present invention has a high capacity and a good cycle life. Because of its excellent thermal properties, it is possible to provide tablet devices that can be used for long periods of time. do.

[0250] In addition, the tablet terminals shown in Figs. 18(A) and 18(B) can be used in various Functions that display information (still images, videos, text images, etc.), calendars, dates, or times A function to display information on the display unit, and a function to input or edit information displayed on the display unit. It has input functions, functions to control processing by various software (programs), etc. It is possible.

[0251] The solar cell 9633 attached to the surface of the tablet device supplies power to the touch panel, The solar cell 9633 can be provided to a display unit, a video signal processor, or the like. The structure can be provided on one or both sides of the power storage unit 9630, and can efficiently charge the power storage unit 9635. It can be said that it is completed.

[0252] The configuration and operation of the charge / discharge control circuit 9634 shown in FIG. A block diagram is shown in FIG. 18C. 5, DC-DC converter 9636, converter 9637, switches SW1 to SW3, table The display unit 9631 is shown, which includes a storage battery 9635, a DC-DC converter 9636, and a The inverter 9637 and the switches SW1 to SW3 are connected to the charge / discharge control circuit 96 shown in FIG. This corresponds to 34.

[0253] First, an example of operation in which power is generated by the solar cell 9633 using external light will be described. The power generated by the solar cell is converted to a voltage for charging the storage battery 9635 by the DCDC controller. The voltage is increased or decreased by a inverter 9636. When power from the 9633 is used, switch SW1 is turned on and the converter 9637 The voltage is increased or decreased to a voltage required for the display unit 9631. When not displaying the battery status, turn SW1 off and SW2 on to charge the battery 9635. The configuration may be such that the power supply is electrically connected to the power source.

[0254] The solar cell 9633 is shown as an example of a power generating means, but is not limited thereto. Storage of electricity by other power generation means such as piezoelectric elements and thermoelectric conversion elements For example, the device may be configured to transmit and receive power wirelessly (contactlessly). It is also possible to combine it with a non-contact power transmission module that charges the battery by using other charging methods. This is also fine.

[0255] FIG. 19 shows another example of electronic equipment. In FIG. 19, a display device 8000 according to one embodiment of the present invention is 8 is an example of an electronic device using a secondary battery 8004 according to an embodiment. 8000 corresponds to a display device for receiving TV broadcasts, and includes a housing 8001, a display unit 8002, and a speaker unit. The secondary battery 8004 according to one embodiment of the present invention includes a housing. The display device 8000 is provided inside a body 8001. The display device 8000 receives power from a commercial power source. Alternatively, the power stored in the secondary battery 8004 can be used. Even when power cannot be supplied from a commercial power source due to a power outage or the like, the present invention according to one embodiment of the present invention can be used. By using the secondary battery 8004 as an uninterruptible power supply, the display device 8000 can be used. do.

[0256] The display unit 8002 may be a liquid crystal display device, an emitting device having light emitting elements such as organic EL elements in each pixel, or the like. Device, electrophoretic display device, DMD (Digital Micromirror Devi ce), PDP (Plasma Display Panel), FED (Field A semiconductor display device such as a 3D Emission Display can be used.

[0257] In addition, display devices are used for TV broadcast reception, personal computers, advertising displays, etc. , all display devices for displaying information are included.

[0258] In FIG. 19, a stationary lighting device 8100 includes a secondary battery 81 according to one embodiment of the present invention. 8101, a light source 8102, and a light source 8103 are used. 19, the secondary battery 8103 is disposed in the housing 81. 8102 is installed inside a ceiling 8104. However, the secondary battery 8103 may be provided inside the housing 8101. The device 8100 can receive power from a commercial power source, or store power in a secondary battery 8103. Therefore, when the power supply from the commercial power source is cut off due to a power outage, Even when the electricity cannot be received, the secondary battery 8103 according to one embodiment of the present invention is used as an uninterruptible power source. This enables the lighting device 8100 to be used.

[0259] In addition, FIG. 19 illustrates a lighting device 8100 that is installed on a ceiling 8104. However, in the secondary battery according to one embodiment of the present invention, other than the ceiling 8104, for example, the side wall 8105, the floor 8106, 106, the window 8107, etc., can be used as a fixed lighting device, or a tabletop lighting device. The present invention can also be used in lighting devices of this type.

[0260] In addition, the light source 8102 may be an artificial light source that artificially obtains light using electricity. Specifically, incandescent lamps, fluorescent lamps and other discharge lamps, light emitting diodes (LEDs) and organic electroluminescence (EL) elements The element is an example of the artificial light source.

[0261] In FIG. 19, an air conditioner having an indoor unit 8200 and an outdoor unit 8204 is as follows: 8 is an example of an electronic device using a secondary battery 8203 according to one embodiment of the present invention. The device 8200 includes a housing 8201, an air outlet 8202, a secondary battery 8203, and the like. 8 illustrates an example in which the secondary battery 8203 is provided in the indoor unit 8200. The battery 8203 may be provided in the outdoor unit 8204. A secondary battery 8203 may be provided in both the power source 8202 and the power source 8204. The power supply can be provided from a commercial power source, or the power stored in the secondary battery 8203 can be used. In particular, a secondary battery 82 is provided in both the indoor unit 8200 and the outdoor unit 8204. If 03 is installed, when power cannot be supplied from the commercial power source due to a power outage, etc. In addition, by using the secondary battery 8203 according to one embodiment of the present invention as an uninterruptible power supply, The conditioner can be used.

[0262] In Figure 19, a separate type air conditioner consisting of an indoor unit and an outdoor unit is shown. As an example, an all-in-one air conditioner that has both indoor and outdoor unit functions in a single housing. The secondary battery according to one embodiment of the present invention can also be used for the conditioner.

[0263] In FIG. 19, an electric refrigerator-freezer 8300 includes a secondary battery 8304 according to one embodiment of the present invention. Specifically, an electric refrigerator-freezer 8300 includes a housing 8301, a refrigerator It has a storage compartment door 8302, a freezer compartment door 8303, a secondary battery 8304, etc. A secondary battery 8304 is provided inside the housing 8301. The electric refrigerator-freezer 8300 is It can receive power from a commercial power source, or use the power stored in the secondary battery 8304. Therefore, when power cannot be supplied from commercial power sources due to a power outage, etc. However, by using the secondary battery 8304 according to one embodiment of the present invention as an uninterruptible power supply, It will be possible to use the 8300 freezer refrigerator.

[0264] In addition, during periods when electronic devices are not in use, especially during periods when the total amount of power that can be supplied by commercial power suppliers is low, During times when the ratio of electricity actually used (called the electricity usage rate) is low, By storing power in the battery, it is possible to prevent high power usage outside of the above time periods. For example, in the case of the electric refrigerator-freezer 8300, when the temperature is low, the refrigerator compartment door 830 2. During the night when the freezer door 8303 is not opened or closed, the secondary battery 8304 stores electricity. Then, as the temperature rises, the refrigerator door 8302 and the freezer door 8303 are opened and closed. During the daytime, when the vehicle is turned on, the secondary battery 8304 is used as an auxiliary power source, and the daytime power usage rate is can be kept low.

[0265] In addition to the electronic devices described above, the secondary battery of one embodiment of the present invention can be mounted on various electronic devices. According to one embodiment of the present invention, the cycle characteristics of the secondary battery can be improved. According to this aspect, a high-capacity secondary battery can be obtained, and therefore the secondary battery itself can be made small and lightweight. Therefore, the secondary battery according to one embodiment of the present invention can be By incorporating this in electronic devices, the electronic devices can have a longer life and become lighter in weight. The embodiment can be implemented in appropriate combination with other embodiments.

[0266] (Embodiment 5) In this embodiment, an example in which a secondary battery according to one embodiment of the present invention is mounted on a vehicle will be described.

[0267] When a secondary battery is installed in a vehicle, it becomes a hybrid vehicle (HEV), electric vehicle (EV), or powertrain. This will make it possible to realize next-generation clean energy vehicles such as plug-in hybrid vehicles (PHEVs). .

[0268] FIG. 20 illustrates an example of a vehicle using a secondary battery according to one embodiment of the present invention. The automobile 8400 shown in FIG. 1 is an electric automobile that uses an electric motor as a power source for driving. Alternatively, an electric motor and an engine can be selected as the power source for driving. By using one embodiment of the present invention, the cruising distance can be extended. In addition, the automobile 8400 has a secondary battery. 12(C) and 12(D) are mounted on the floor of the vehicle. In addition, a battery pack using multiple secondary batteries as shown in FIG. The secondary battery may be installed on the floor of the vehicle. In addition, it supplies power to light-emitting devices such as headlights 8401 and room lights (not shown). can be provided.

[0269] In addition, the secondary battery is used for the display of the speedometer, tachometer, etc. of the automobile 8400. The secondary battery can supply power to the navigation device of the automobile 8400. The present invention can provide power to semiconductor devices such as power distribution systems.

[0270] The automobile 8500 shown in FIG. 20(B) is a secondary battery that is plugged in. The device can be charged by receiving power from an external charging facility using a contactless charging method or other methods. FIG. 20(B) shows a diagram of a charging device 8021 mounted on a ground and a charging station 8022 mounted on a vehicle 8500. The secondary battery 8024 is shown being charged via a cable 8022. For charging methods and connector specifications, please refer to the designated specifications of CHAdeMO (registered trademark) or Combo. The charging device 8021 is a charging station installed in a commercial facility. For example, plug-in technology can be used to The secondary battery 8024 installed in the automobile 8500 can be charged by the power supply. Charging is performed by converting AC power to DC power via a conversion device such as an ACDC converter. It is possible.

[0271] Although not shown, a power receiving device is mounted on the vehicle and receives power from a ground power transmitting device in a non-contact manner. In this non-contact power supply method, a power transmission device is installed on the road or exterior wall. By incorporating this technology, charging can be done not only when the vehicle is stopped but also while it is moving. Using this method, electric power may be transmitted between vehicles. A solar battery may be installed to charge the secondary battery when the vehicle is stopped or running. The power can be supplied using an electromagnetic induction method or a magnetic resonance method.

[0272] FIG. 20C shows an example of a two-wheeled vehicle using the secondary battery of one embodiment of the present invention. The scooter 8600 shown in (C) has a secondary battery 8602, side mirrors 8601, and a turn signal. The secondary battery 8602 can supply electricity to the direction indicator light 8603. can.

[0273] In addition, the scooter 8600 shown in FIG. 20(C) has a secondary battery 860 in the storage space under the seat 8604. 2 can be stored. The secondary battery 8602 can be stored in the under-seat storage 8604 even if it is small. The secondary battery 8602 can be removed and stored in the under-seat storage 8604. It is preferable that the secondary battery 8602 is carried indoors for charging, and then the secondary battery 8602 is charged and driven. It is preferable to store the device before carrying out the procedure.

[0274] According to one aspect of the present invention, the cycle characteristics of the secondary battery are improved, and the capacity of the secondary battery is increased. Therefore, the secondary battery itself can be made smaller and lighter. If the body can be made smaller and lighter, it will contribute to reducing the weight of the vehicle, which will improve the driving range. In addition, the secondary battery installed in the vehicle can also be used as a power supply source for purposes other than the vehicle. In this case, for example, it is possible to avoid using commercial power sources during peak power demand periods. If we can avoid using commercial power sources during peak power demand periods, we can save energy and This can contribute to reducing carbon dioxide emissions. In addition, if the cycle characteristics are good, Since the secondary battery can be used for a long period of time, the amount of rare metals used, including cobalt, can be reduced. It is possible.

[0275] This embodiment mode can be implemented in appropriate combination with other embodiment modes. EXAMPLES

[0276] In this example, cobalt was used as the transition metal contained in the first region in the positive electrode active material. And a positive electrode active material prepared by adding magnesium and fluorine to the starting material, and a comparative example We prepared a positive electrode active material without adding magnesium or fluorine and analyzed its characteristics. In addition, the cycle characteristics were evaluated by changing the concentrations of magnesium and fluorine added to the starting material. Evaluated.

[0277] <Preparation of Positive Electrode Active Materials for Samples 1 to 6> The positive electrode activity of samples 1 to 6 was evaluated by changing the concentration of the magnesium source and the fluorine source. The materials were prepared using lithium carbonate and cobalt oxide as common starting materials. Magnesium oxide and lithium fluoride were used as starting materials, which were different for each sample.

[0278] Sample 1 is made of 0.5 atomic % mag with respect to the cobalt contained in the common starting material. Magnesium oxide and fluorine are added to the mixture so that it contains 1 atomic % of fluorine and 1 atomic % of selenium. Lithium fluoride was used as the starting material for the additive. It is written as 1mol% MgO and 1mol% LiF.

[0279] As described above, in this specification, the amount of the added starting material is determined based on the transition metal contained in the common starting material. The same applies to sample 2 and onwards. It is written as follows.

[0280] Sample 2 contains 0.5 mol% MgO, 0.5 mol% cobalt as starting material. Sample 3 was made of 0.5 mol% MgO as an additive starting material, Sample 4 is a comparative example, and contains 1 mol LiF as the starting material. % LiF was used, and no magnesium was added. Sample 5 was used as a comparative example. The emitting material was 0.5 mol% MgO, and no fluorine was added. As a control, neither magnesium nor fluorine was added. The starting materials and additive starting materials are shown in Table 1.

[0281] [Table 1]

[0282] The above six samples were prepared by the same method as described in the first embodiment. The ingredients are mixed, heated for the first time, cooled, sieved, heated for the second time, cooled, and The particles in the middle of these steps and those after these steps were collected to obtain a positive electrode active material. The positive electrode active material was analyzed as follows.

[0283] <stem-edx> For Sample 1 and Sample 5 (comparative example), the cross-section near the surface of the particles before the second heating was analyzed using STEM-EDX. Figures 22 and 23 show the STEM-EDX images of Sample 1 before the second heating and Sample 5 (comparative example) before the second heating, respectively. Figures 22(A) and 23(A) are STEM images, Figures 22(B) and 23(B) are magnesium mappings, and Figures 22(C) and 23(C) are fluorine mappings. As shown in Figure 22(B), in Sample 1 containing magnesium and fluorine in the starting material,

[0284] it was observed that magnesium was segregated to some extent near the surface of the particles even before the second heating. The segregated region was about 1 nm to 2 nm from the surface of the particles.

[0285] On the other hand, as shown in the EDX mapping of Figure 23(B), in Sample 5 containing magnesium but not containing fluorine in the starting material, segregation of magnesium to the vicinity of the surface was not observed.

[0286] As shown in Figures 22(C) and 23(C), almost no fluorine was observed inside the positive electrode active material in both Sample 1 and Sample 5. This was considered to be because fluorine, which is a light element, is difficult to detect by EDX.

[0287] <X-ray Photoelectron Spectroscopy (XPS)> Next, for Sample 1 and Sample 5 (comparative example), the amount of magnesium near the surface of the positive electrode active material before and after the second heating was analyzed.

[0288] The conditions for XPS analysis were as follows. Measuring device: QuanteraII manufactured by PHI ​​X-ray source: Monochromated Al (1486.6 eV) Detection area: 100μmφ Detection depth: Approx. 4 to 5 nm (take-off angle 45°) Measurement spectrum: Wide, Li1s, Co2p, Ti2p, O1s, C1s, F1s, S 2p, Ca2p, Mg1s, Na1s, Zr3d

[0289] The results of quantifying the concentration of each element using XPS are shown in Table 2. The quantitative accuracy is ±1 atom. The detection limit is about 1 atomic%, depending on the element. The quantification error is larger than normal due to the removal of the isolated Mg Auger peak.

[0290] Table 3 shows the results of calculating the abundance ratio of each element when cobalt is set to 1.

[0291] [Table 2]

[0292] [Table 3]

[0293] In addition, the abundance ratio of magnesium among the elements shown in Table 3 is shown in Figure 2. Shown in 4.

[0294] As shown in Tables 2 and 3 and FIG. 24, the starting materials magnesium and fluorine were added. In sample 1, even before the second heating, there was magnesium near the surface of the positive electrode active material that could be measured by XPS. After the second heating, the amount of magnesium near the surface of the positive electrode active material was further increased. It increased.

[0295] In other words, it is believed that the second heating promoted the segregation of magnesium onto the surface of the positive electrode active material. In this way, the positive electrode active material of Sample 1 has a first region inside and a second region on the surface layer. a first region having lithium cobalt oxide and a second region having magnesium oxide; It was confirmed that this was an active material.

[0296] On the other hand, in sample 5, which does not have fluorine as an added starting material and has only magnesium, Both before and after the second heating, magnesium near the surface of the positive electrode active material was below the detection limit. In other words, the fluorine contained in the starting material unexpectedly causes magnesium to segregate in the surface layer of the positive electrode active material. It became clear that there was an effect of

[0297] <Cycle characteristics> Next, Sample 1 before and after the second heating, Sample 5 before and after the first heating, and Sample 2, The positive electrode active materials of Sample 3, Sample 4, and Sample 6 were used to make a CR2032 type (diameter 2 A coin-type secondary battery (size 0.0 mm and height 3.2 mm) was fabricated and its cycle characteristics were evaluated.

[0298] The positive electrode was made of the positive electrode active material prepared above, acetylene black (AB), and polyvinyl chloride (PFC). Positive electrode active material: AB:PVDF=95:2.5:2.5 (weight ratio) The slurry mixed in the above step was applied to the current collector.

[0299] Lithium metal was used as the counter electrode.

[0300] The electrolyte used in the electrolytic solution is 1 mol / L lithium hexafluorophosphate (LiPF6). The electrolyte contains ethylene carbonate (EC) and diethyl carbonate (DEC). C:DEC=3:7 (volume ratio), vinylene carbonate (VC) was mixed at 2% by weight. The following was used.

[0301] The positive electrode can and the negative electrode can were made of stainless steel (SUS).

[0302] The measurement temperature for the cycle characteristic test was 25°C. Charging was performed at a current density of 68 The current density was then set at 1.4mA / g, with a constant current of 0.5mA / g and an upper limit voltage of 4.6V. The battery was charged at a constant voltage up to 1000 V. The battery was discharged at a constant voltage of 68.5 mA / g per unit weight of active material. The charge / discharge cycle was performed at a current of 100 mA and a lower limit voltage of 2.5 V. 30 charge / discharge cycles were performed for each battery.

[0303] 25(A) and 25(B) show the results of the first and second heating of sample 1 and the first heating of sample 5. FIG. 25(A) shows a graph of the cycle characteristics of a secondary battery using the positive electrode active material of FIG. 1 before and after heating. ) is the energy density when charged to 4.6V, and Fig. 25(B) is the energy density when charged to 4.6V. 1 is a graph showing the retention rate. The energy density is the product of the discharge capacity and the average discharge voltage.

[0304] As shown in FIG. 25, in sample 1 having magnesium and fluorine in the added starting material, The cycle characteristics were significantly improved by heating the battery in step 2. The energy density was also good. Ta.

[0305] As was made clear from the XPS results mentioned above, the positive This is believed to be due to an increase in the amount of magnesium present near the surface of the electrode active material.

[0306] On the other hand, in sample 5, which has only magnesium in the added starting material, the No significant difference was observed in the cycle characteristics.

[0307] Next, in FIG. 26 and FIG. 27, the positive electrode active materials of Samples 1 to 6 after the second heating are used. FIG. 26 shows a graph of the cycle characteristics of the secondary battery. FIG. 27 is a graph of the energy density maintenance rate when charged to 4.6V.

[0308] As shown in FIGS. 26 and 27, Sample 4 (Comparative Example 1) in which only fluorine was added to the starting material ), and sample 5 (comparison example) to which only magnesium was added had a low fluorine content. Both samples showed inferior cycle characteristics to Sample 6 (Comparative Example) in which no additive was added.

[0309] On the other hand, samples 1 to 3, which had magnesium and fluorine added to the starting material, were good. The best cycle characteristics were observed for magnesium and fluorine. The atomic ratio of magnesium to fluorine was 1:2 in sample 1. Sample 2, in which the ratio is 1:4, exhibited good cycle characteristics. As shown, not only the cycle characteristics but also the energy density were good.

[0310] In this way, adding magnesium and fluorine to the starting material provides good cycle characteristics. It was also revealed that the magnesium contained in the starting material can be used to obtain a positive electrode active material. The atomic ratio of Mg to fluorine is preferably Mg:F=1:x (1.5≦x≦4). It was found that a ratio of about 1:2 was most preferable.

[0311] <Preparation of positive electrode active materials for samples 7 and 8> Next, the amount of magnesium added was changed while keeping the ratio of magnesium to fluorine constant (Mg:F=1:2). Then, positive electrode active materials of Samples 7 and 8 were prepared.

[0312] Sample 7 used 1 mol % MgO and 2 mol % LiF as additive starting materials. Sample 8 used 2 mol% MgO and 4 mol% LiF as additive starting materials. Samples 7 and 8 were fabricated by the same method as described in the first embodiment. Similarly, the starting materials are mixed, heated a first time, cooled, sieved, and heated a second time. The mixture was cooled and recovered to prepare a positive electrode active material, and a secondary battery was then prepared.

[0313] The atomic ratio of magnesium to fluorine in the raw material is Mg:F=1:2. Sample 7, Sample 8, and a comparative sample without magnesium or fluorine added The 6 common starting materials and additional starting materials are shown in Table 4.

[0314] [Table 4]

[0315] <Cycle characteristics> Figure 28(A) and Figure 28(B) show sample 1, sample 7, sample 8 and sample FIG. 28 shows a graph of the cycle characteristics of a secondary battery using the positive electrode active material of Example 6 (Comparative Example). A) is a graph of the energy density when charging at 4.6V, and Figure 28(B) is a graph of the energy density when charging at 4.6V. 1 is a graph showing the energy density maintenance rate.

[0316] As shown in FIG. 28(A) and FIG. 28(B), the atomic ratio of magnesium to fluorine in the raw material All samples with Mg:F=1:2 showed good cycle characteristics. The best result was obtained from sample 7, which used 1 mol% MgO and 2 mol% LiF as starting materials. The battery showed good cycle characteristics, with the energy density retention rate after 30 cycles being 93%. As is clear from Figure 28(A), not only the cycle characteristics but also the energy density are good. there were. EXAMPLES

[0317] In this example, a positive electrode active material having a second region formed by segregation of magnesium, Comparison of positive electrode active materials with magnesium oxide layers formed by external coating The following is shown.

[0318] <Positive electrode active material having second region formed by segregation> As a positive electrode active material having a second region formed by segregation of magnesium, Sample 7 of Example 1, which uses 1 mol% MgO and 2 mol% LiF as materials, Used.

[0319] <Positive electrode active material with externally coated MgO> As a positive electrode active material having a magnesium oxide layer formed by coating from the outside, Sample 9: Lithium ruthenium oxide coated with magnesium oxide using polygonal barrel sputtering The positive electrode active materials of Sample 9 (Comparative Example) and Sample 10 (Comparative Example) were used. The method for producing Sample 10 (Comparative Example) will be described below.

[0320] The lithium cobalt oxide used was made by Nippon Kagaku Kogyo Co., Ltd. (product name: C-10N). The sputtering target was magnesium oxide, the power was 450 W, and the sputtering gas was The partial pressures of Ar and O2 were 0.6 Pa and 0.6 Pa, respectively. The treatment time was 36 minutes for sample 9 and 180 minutes for sample 10. .

[0321] After polygonal barrel sputtering, STEM observation revealed that the positive electrode active material in sample 9 A magnesium oxide layer of about 1 to 3 nm was attached to the surface. A magnesium oxide layer of about 6 nm to 8 nm was attached to the surface of the positive electrode active material.

[0322] Thereafter, Samples 9 and 10 were subjected to the second heating in the same manner as described in the first embodiment. The sample was heated to 800°C for 2 hours. The temperature was increased by 200°C / h, and dry air with a dew point of -109°C was blown for 10 min. The flow rate was 1 L / min.

[0323] Sample 7, Sample 9 (Comparative Example), and Sample 10 (Comparative Example) to be Compared in this Example The conditions are shown in Table 5.

[0324] [Table 5]

[0325] <stem> Cross sections of the positive electrode active materials of Sample 7 and Sample 10 (Comparative Example) were observed using STEM. Figures 29(A) and 29(B) show a sample with a second region formed by segregation. The STEM images of sample 7 are shown in Fig. 30(A) and (B). 1 shows a STEM image of Sample 10 (Comparative Example) having a magnesium oxide layer formed thereon.

[0326] In sample 7, the fact that the first and second regions are different regions results in differences in the brightness of the image. As shown in Figure 29, the second region formed by segregation was In sample 7 having the above structure, a second region of about 1 nm to 2 nm was observed.

[0327] In addition, in the case of sample 10 (comparative example), as shown in FIG. The formation of a magnesium oxide layer was observed from the difference in brightness of the image. In Sample 10 (Comparative Example), a magnesium oxide layer of about 8 nm was observed.

[0328] In both Sample 7 and Sample 10 (Comparative Example), the cations and anions between the different layers The arrangement of the first and second regions is at least partially aligned, and the crystal orientation of the first and second regions is consistent. It was observed that the

[0329] <Charge / discharge characteristics> Using the positive electrode active materials of Sample 7, Sample 9 (Comparative Example) and Sample 10 (Comparative Example), A secondary battery was fabricated in the same manner as in Example 1, and the charge / discharge characteristics were evaluated. 31B shows the positive electrode of Sample 9 (Comparative Example), and FIG. 31C shows the positive electrode of Sample 10 (Comparative Example). 1 shows a graph of charge / discharge characteristics of a secondary battery using the active material.

[0330] As shown in FIG. 31, the sample had a second region formed by magnesium segregation. 7 is better than sample 9, which has a magnesium oxide layer formed by polygonal barrel sputtering. The capacity was larger than that of Sample 10, and the charge-discharge characteristics were good.

[0331] <Cycle characteristics> Next, the positive electrode active materials of Sample 7, Sample 9 (Comparative Example) and Sample 10 (Comparative Example) were The results of evaluating the cycle characteristics of the secondary battery used are shown in FIG. 32(A) and FIG. 32(B). The cycle characteristic test was carried out in the same manner as in Example 1.

[0332] Figure 32(A) shows the energy density when charging at 4.6V, and Figure 32(B) shows the energy density when charging at 4.6V. As shown in FIG. 32(B), the first layer formed by segregation is Sample 7, which has the region 2, is superior to sample 7, which has the region 3 formed by polygonal barrel sputtering. The cycle characteristics are significantly better than those of Samples 9 and 10, which have a silicon layer. In addition, as shown in FIG. 32(A), the energy density was also better in sample 7.

[0333] Thus, the second region formed by magnesium segregation was observed in polygonal barrel sputtering. This contributes to better charge / discharge and cycle characteristics than the magnesium oxide layer formed by It became clear that.

[0334] From these results, it is considered that the magnesium oxide layer covering the lithium cobalt oxide particles from the outside is more effective. rather, it was formed as a result of magnesium that was already included in the starting material segregating to the surface. The magnesium-containing region contributes to stabilizing the crystal structure of lithium cobalt oxide. was speculated. EXAMPLES

[0335] In this example, the characteristics of the positive electrode active material having a second region formed by segregation of magnesium are The characteristics were revealed by various analyses.

[0336] <Analyzed cathode active material> The sample of Example 1 was prepared by adding 1 mol% MgO and 2 mol% LiF as starting materials. Ple 7 was used as the analytical sample in this example.

[0337] <STEM、FFT> S of the cross section near the surface of the positive electrode active material of sample 7 having the second region formed by segregation TEM-FFT images are shown in Figures 33 and 34. Figure 33(A) shows the surface of the positive electrode active material. This is a STEM image, and the FFT (Fast Fourier Transform) of the area indicated by FFT1 in Fig. 33(A) is ) image is shown in Figure 33(B). Some of the bright spots in the FFT image of Figure 33(B) are shown in Figure 33(C). We decided to call them A, B, C, and O.

[0338] For the bright spots in the FFT image of the area shown in FFT1, the actual measured values ​​are OA, d=0.2 0 nm, OB was d=0.24 nm, and OC was d=0.25 nm. Also, ∠AOB=5 3°, ∠BOC=74°, ∠AOC=127°.

[0339] This is the ICDD (International Centre for Diffra Magnesium oxide (MgO) data in the I OA(200) d=0.21nm, OB(1 -11) d = 0.24 nm, OC(-1-11) d = 0.24 nm, ∠AOB = 55 ∠BOC=70°, ∠AOC=125°. Therefore, the area shown in FFT1 is It was revealed that this region has a rock-salt type crystal structure and is an image of the

[0011] incidence. .

[0340] FIG. 34(A) is a STEM image of the surface of the same positive electrode active material as in FIG. 33(A). The FFT image of the area indicated by FFT2 in A) is shown in Fig. 34(B). Some of the bright spots in the image are designated A, B, C, and O, as shown in Figure 34(C).

[0341] For the bright spots in the FFT image of the area shown in FFT2, the actual measured values ​​are OA, d=0.2 4 nm, OB was d=0.20 nm, and OC was d=0.45 nm. Also, ∠AOB=2 5°, ∠BOC=53°, ∠AOC=78°.

[0342] This is based on the data for lithium cobalt oxide (LiCoO2) in the ICDD database ( OA(101) d=0.24nm, OB( 104) d = 0.20 nm, OC(003) d = 0.47 nm, ∠AOB = 25°, ∠BOC=55°, ∠AOC=80° are close. Therefore, the area shown by FFT2 is It was revealed that the region had lithium ruthenium oxide and was an image of the

[0010] incidence.

[0343] In addition, the STEM images in Figures 33(A) and 34(A) show that the first and second regions The brightness of the images was different, and the crystal orientation was consistent between the first and second regions. It was observed that

[0344] <stem-edx> Next, the surface and crystal defect areas of sample 7 were analyzed using STEM-EDX. The results are shown in Figures 35 to 37.

[0345] FIG. 35 shows the results of STEM-EDX analysis of the surface area of ​​the positive electrode active material of Sample 7. (A) is a STEM image, (B) is magnesium mapping, and (C) is fluorine mapping. This is a mapping of

[0346] As in Example 1, 0.5 mol% MgO and 1 mol% LiF were used as additive starting materials. Starting material with 1 mol% MgO and 2 mol% LiF added compared to sample 1 (Figure 22) In sample 7 (Figure 35), magnesium is clearly visible near the surface of the positive electrode active material. This is because the greater the amount of magnesium near the surface of the positive electrode active material, the greater the cycle characteristics. This supports the results of Example 1, which shows that the antibacterial effect is good.

[0347] FIG. 36 is a cross-sectional TEM image of the vicinity of a crystal defect in the positive electrode active material of Sample 7. In 1001, a bright area that appears to be a crystal defect was observed.

[0348] The crystal defect 1001 in Figure 36 was analyzed using STEM-EDX and the results are shown in Figure 37. show.

[0349] Figure 37(A-1) is a STEM image of the crystal defect 1001, and Figure 37(A-2) is a STEM image of magnesium. Figure 37(B-1) is a mapping of fluorine, and Figure 37(B-2) is a mapping of zirconium. This is a mapping of Um.

[0350] As shown in FIG. 37(A-2), the crystal defects and their vicinity in the positive electrode active material of Sample 7 Therefore, magnesium segregation was observed not only near the surface but also in the interior of sample 7. It was also shown that the positive electrode active material has a second region. As shown in the figure, zirconium segregation was also observed in the second inner region. The process is carried out using a ball mill, which is made of zirconium. Therefore, it is possible that zirconium was mixed into sample 7. ) almost no fluorine was detected in the second inner region, which is due to EDX. This was thought to be because fluorine, a light element, is difficult to detect in the atmosphere.

[0351] <tof-sims> Next, the positive electrode active material of sample 7 having the second region formed by segregation was subjected to a magnetron sputtering test. To investigate the depth distribution of nesium and fluorine, ToF-SIMS was used for analysis. The results are shown in FIG.

[0352] Using multiple positive electrode active material particles as samples, ToF-SIMS analysis and sputtering were performed alternately. The analysis was repeated from the surface of the positive electrode active material in the depth direction. The IMS5-300 (manufactured by ION-TOF) was used as the sputtering ion source. The analysis was carried out over an area of ​​approximately 50 μm square.

[0353] Magnesium oxide ion ([MgO2] 2- ) and fluorine ion (F - ) strength, The horizontal axis is the number of measurements (cycles) and the graph is shown in Figure 38. Since the analysis is done on ions, the distribution of magnesium is [MgO2] 2- With an intensity of The intensity was normalized with the maximum value set to 1.

[0354] As shown in FIG. 38, the sample had a second region formed by magnesium segregation. 7, it was found that the magnesium and fluorine depth profiles and peaks overlap. Ta.

[0355] <xps> Next, the positive electrode active material of Sample 7 was analyzed by XPS before and after the second heating. The results are shown in Table 6 and Fig. 39. The XPS analysis was carried out in the same manner as in Example 1.

[0356] The results of quantifying the concentration of each element in sample 7 using XPS are shown in Table 6. The detection limit is about ±1 atomic%, and the detection limit is about 1 atomic%, depending on the element. In the case of Ca, the quantitative error is larger than usual because the waveform-separated Mg Auger peak is removed. big.

[0357] [Table 6]

[0358] The quantitative values ​​in Table 6 are from a depth of 4 nm from the surface to the center of the positive electrode active material, which is possible to analyze with XPS. They exist in the range from 0.5 nm to 5 nm and are composed of lithium, cobalt, titanium, oxygen, carbon, fluorine, and sulfur. , calcium, magnesium, sodium and zirconium total amount 100atom This is the value when it is set to c%.

[0359] As shown in Table 6, after the second heating, the sample having the second region formed by segregation 7, in the range of 4 nm to 5 nm deep from the surface toward the center, lithium, Barium, titanium, oxygen, carbon, fluorine, sulfur, calcium, magnesium, sodium and When the total amount of magnesium and zirconium is 100%, the magnesium concentration is 5.5 atomic percent. %, and the fluorine concentration was 1.4 atomic %.

[0360] The total amount of lithium, cobalt, oxygen, fluorine, and magnesium is 100%. The magnesium concentration was calculated to be 6.7%, and the fluoride concentration was calculated to be 1.7%. .

[0361] The ratio of magnesium to fluorine concentrations is in the range of Mg:F=y:1 (3≦y≦5). More precisely, the Mg:F ratio was about 3.9:1.

[0362] Next, the bonding state of fluorine in Sample 7 after the second heating was analyzed by surface XPS analysis. The results are shown in FIG. 39. As a comparative example, 10 mol% LiF was used as the starting material. The results are for a sample prepared in the same manner as sample 7, except that no magnesium was added. The XPS spectra of standard samples of MgF2 and LiF are also shown.

[0363] As shown in Figure 39, 10 mol% LiF was used as the starting material, and magnesium was added. In the undoped sample, the fluorine binding energy peak is consistent with LiF. 5 eV, and LiF is the main bond for fluorine present in the surface layer of the positive electrode active material. On the other hand, the starting material containing 1 mol% MgO and 2 mol% LiF In sample 7 having the second region, the fluorine present in the surface layer of the positive electrode active material was The binding energy peak is between 682 eV and 685 eV, more precisely 684.3 e V, which did not match either MgF2 or LiF. It is presumed that the fluorine in the region exists in a bond state other than MgF2 and LiF. Ta. EXAMPLES

[0364] In this example, the first step of producing a positive electrode active material having a second region formed by segregation was performed. The results of the investigation into the temperature of the second heating and the atmosphere during the second heating are explained below. .

[0365] <Second heating temperature> <Preparation of Positive Electrode Active Materials for Samples 11 to 13> The temperature of the second heating was changed to prepare positive electrode active materials of Samples 11 to 13. All of the materials used were lithium carbonate and cobalt oxide as starting materials, and the additive starting materials were The materials used were 1 mol% MgO and 2 mol% LiF.

[0366] The temperature of the second heating was 700° C. for sample 11, 900° C. for sample 12, and A positive electrode active material was prepared in the same manner as in Sample 7 of Example 1, except that the temperature was set to 1000° C. The temperature of the second heating of sample 7 is 800° C. The temperature of the second heating of each sample is shown in Table 7. vinegar.

[0367] [Table 7]

[0368] Using the positive electrode active materials of Sample 7, Sample 11 to Sample 13, two The following batteries were fabricated and the cycle characteristics were evaluated. The cycle characteristics are shown in Figure 40. The charge and discharge conditions were the same as in Example 1.

[0369] Figure 40(A) is a graph of the energy density when charging at 4.6V, and Figure 40(B) is a graph of the energy density when charging at 4.6V. 40(B) is a graph showing the energy density maintenance rate at the second heating temperature. Sample 7, in which the second heating temperature was set to 800°C, showed the best cycle characteristics. Sample 11 at 0°C and Sample 12 at 900°C were the next best cycles. Even in sample 13, where the second heating temperature was 1000°C, after 20 cycles The energy density retention rate was 76%. This is the same as the case without added starting material shown in Figure 26. In sample 6, the energy density retention rate after 20 cycles was 63%. This indicates that the battery exhibited good cycle characteristics.

[0370] Therefore, the temperature of the second heating is preferably 700°C or more and 1000°C or less, and more preferably 700°C or more and 900°C or less. It was found that a temperature of 00°C or lower is more preferable, and a temperature of about 800°C is even more preferable.

[0371] <Second heating atmosphere> <Preparation of Positive Electrode Active Materials for Samples 14 to 16> The atmosphere in the second heating was changed from dry air to 100% oxygen, from sample 14 to sample 1 The positive electrode active materials were prepared up to 6. All the starting materials were lithium carbonate and and cobalt oxide, and 1mol% MgO and 2mol% LiF were used as additive starting materials. The second heating was performed in an oxygen atmosphere. Samples 7, 12, and 13 were A positive electrode active material was prepared in the same manner.

[0372] Using the positive electrode active materials of Samples 14 to 16, secondary batteries were fabricated in the same manner as in Example 1. The cycle characteristics were evaluated together with Samples 7, 12, and 13.

[0373] Energy density and cycle characteristics of sample 7, sample 12 to sample 16 The graphs are shown in Figure 41 and Figure 42. Figure 41 shows the energy density, and Figure 42 shows the cycle characteristics. 41(A) and 42(A) are graphs showing the results when the temperature of the second heating was set to 800° C. Sample 14 and Sample 7, Fig. 41(B) and Fig. 42(B) are samples heated to 900°C. Sample 15 and Sample 12, and Fig. 41(C) and Fig. 42(C) are samples heated to 1000°C. The cycle characteristics of Sample 16 and Sample 13 are shown in Figs. The atmosphere for the second heating of the samples and the temperature for the second heating are shown in Table 8.

[0374] [Table 8]

[0375] As shown in FIG. 41, when the second heating was performed at 800° C., 900° C., and 1000° C., The second heating in an oxygen atmosphere showed better cycle characteristics than in dry air. Ta. EXAMPLES

[0376] In this example, magnesium and fluorine were used as the additive starting materials, and magnesium and fluorine were used as the additive starting materials. The cycle characteristics were compared when elements other than fluorine were used.

[0377] <Comparison between fluorine and chlorine> First, we used magnesium and fluorine as starting materials, and then used chlorine instead of fluorine. The cycle characteristics were compared when

[0378] <Preparation of positive electrode active materials for samples 17 and 18> Sample 7 contains 1 mol% MgO, 2 mol% Sample 17 was made of 1 mol% MgO, 1 mol% LiF, and 1 mol% Sample 18 is a comparative example, and contains 1 mol% MgO, 2 mol% Sample 6 is a comparative example, and does not contain any magnesium, fluorine, or chlorine. No additives were added.

[0379] Samples 7, 17, 18, and 6 were treated in the same manner as in Example 2. Positive electrode active materials were prepared in the same manner, secondary batteries were fabricated using them, and the cycle characteristics were evaluated. The cycle characteristic test was carried out in the same manner as in Example 1.

[0380] <Cycle characteristics> Table 9 shows the starting materials added to each sample and the energy density retention after 20 cycles. Shows the rate.

[0381] [Table 9]

[0382] As shown in Table 9, when chlorine is added instead of fluorine, the cycle characteristics tend to decrease. However, sample 17, which contains 1% each of fluorine and chlorine, showed a The energy density retention rate was over 80%. This was due to the presence of magnesium, fluorine, and chlorine. Compared with sample 6 which did not have either of these, the cycle characteristics were good.

[0383] <Comparison between magnesium and other metals> Next, we used magnesium and fluorine as starting materials, and replaced magnesium with other materials. The cycle characteristics when metals were used were compared.

[0384] <Preparation of Positive Electrode Active Materials for Samples 19 to 29> As a sample using magnesium and fluorine as the added starting material, Sample 7 of Example 1 Sample 19 is a comparative example, and contains 1 mol% MgO, 1 mol% TiO2 and 2mol% LiF were used. Sample 20 is a comparative example. mol% ZrO2 and 2mol% LiF were used. Sample 21 is a comparative example. Sample 22 is a comparative example, and contains 1 mol% TiO2 and 2 mol% LiF. % V2O5, 2 mol% LiF. Sample 23 is a comparative example. ZnO, 2mol% LiF were used. Sample 24 is a comparative example. Sample 25 is a comparative example, and contains 1 mol% Al2O and 2 mol% LiF. O3, and 2 mol% LiF were used. Sample 26 is a comparative example, and contains 1 mol% MoO Sample 27 is a comparative example, and contains 1 mol% SrO, Sample 28 is a comparative example, and contains 1 mol% NaF, 1m ol% LiF was used. Sample 29 is a comparative example, and contains 1 mol% BaO, 2 mol % LiF was used. As a comparative example in which neither fluorine nor any metal was added, Sample 6 of 1 was used.

[0385] Examples of Sample 6, Sample 7, and Sample 19 to Sample 29 Similar to 1, positive electrode active materials were prepared, secondary batteries were fabricated using them, and the cycle characteristics were evaluated. did.

[0386] <Cycle characteristics> Table 10 shows the starting materials added to each sample and the energy density maintained after 20 cycles. Indicates the ownership rate.

[0387] [Table 10]

[0388] As shown in Table 10, when other metals are added instead of magnesium, the cycle characteristics decrease. There was a tendency for

[0389] From these results, it was found that the combination of magnesium and fluorine was used as the additive starting material. It has been shown that this is extremely effective.

[0390] From the previous examples, by adding magnesium and fluorine as the starting material for the positive electrode active material, It was revealed that magnesium segregates on the surface of the positive electrode active material. Since the coating layer is excellent, the cathode active material has high capacity and excellent cycle characteristics. It became clear that...

[0391] Since secondary batteries having such positive electrode active materials have high capacity and long life, they are suitable for use in portable electronic devices. Furthermore, if it is applied to automobiles and other vehicles, it can reduce the power consumption of commercial power sources during peak power demand periods. It is also possible to avoid using other sources of electricity, thus saving energy and reducing carbon dioxide emissions. It can also contribute to reducing EXAMPLES

[0392] In this embodiment, the transition metals in the first region are nickel, manganese, and cobalt. The applied positive electrode active material was prepared and the results of its evaluation will be described.

[0393] <Sample 31, Sample 32> Sample 31 containing magnesium and fluorine and a comparative sample containing magnesium and fluorine Sample 32 was prepared which did not contain fluorine.

[0394] Sample 31 is a mixture of nickel, manganese, and cobalt in the starting material, with magnesium The starting material was 1 atomic % and 2 atomic % of fluorine. The atomic ratio of nickel, manganese, and cobalt was Ni:Mn:Co=1:1:1.

[0395] First, lithium carbonate (Li2CO3) was used as the common starting lithium source. Nickel oxide (NiO) was used as the nickel source, and manganese oxide was used as the manganese source. The cobalt source was cobalt oxide (Co3O4). Magnesium oxide (MgO) was used as the magnesium source for the additive starting material. The source used was lithium fluoride (LiF).

[0396] Each starting material was 0.323 Mn 0.333 Ni 0.333 O2+MgO 0.01 LiF 0.02 The atomic ratio was then calculated as follows:

[0397] Next, the weighed starting materials were mixed using a ball mill.

[0398] Next, the mixed starting materials were calcined. The calcination was performed at 950°C for 10 hours, with a temperature increase rate of 200°C / h. The flow rate of the dry atmosphere was 10 L / min.

[0399] The above process produces lithium, nickel, manganese, cobalt, magnesium, and fluorine-containing Composite oxide particles were synthesized.

[0400] The synthesized composite oxide particles were cooled to room temperature.

[0401] Next, the composite oxide particles were heated to 800°C (heating rate: 200°C / hour), and held at 40°C. The incubation was carried out in a dry air atmosphere for 2 hours.

[0402] The heated powder was cooled to room temperature and crushed. The sieve used had an opening size of 53 μm.

[0403] The particles after the crushing treatment were used as the positive electrode active material of Sample 31.

[0404] Sample 32 was prepared by mixing each starting material with LiCo 0.333 Mn 0.333 Ni 0.333 O2 The weights were weighed to obtain the atomic ratio. The calcination was carried out at 1000°C. The other samples were the same as those in Sample 31. was prepared in the same manner as above.

[0405] The preparation conditions for Samples 31 and 32 are shown in Table 11.

[0406] [Table 11]

[0407] <Cycle characteristics> Next, the positive electrode active materials of Samples 31 and 32 prepared as described above were used. A coin-type secondary battery of the CR2032 type (diameter 20 mm, height 3.2 mm) was fabricated and The wicking characteristics were evaluated.

[0408] The positive electrode was made of the positive electrode active materials of Sample 31 and Sample 32, and acetylene black (AB ) and polyvinylidene fluoride (PVDF) as the positive electrode active material: AB:PVDF=95:2.5 A slurry of the mixture was applied to an aluminum foil current collector. The solvent used was N-methyl-2-pyrrolidone (NMP).

[0409] Lithium metal was used as the counter electrode.

[0410] The electrolyte used in the electrolytic solution is 1 mol / L lithium hexafluorophosphate (LiPF6). The electrolyte contains ethylene carbonate (EC) and diethyl carbonate (DEC). C:DEC=3:7 (volume ratio) was mixed and vinylene carbonate (VC) was added to it. The material was added at 100% by weight.

[0411] The positive electrode can and the negative electrode can were made of stainless steel (SUS).

[0412] The measurement temperature for the cycle characteristic test was 25°C. Charging was performed at a current density of 68 The current density was then set at 1.4mA / g, with a constant current of 0.5mA / g and an upper limit voltage of 4.6V. The battery was charged at a constant voltage up to 1000 V. The battery was discharged at a constant voltage of 68.5 mA / g per unit weight of active material. The current was set at a minimum voltage of 2.5V.

[0413] Discharge ratio of secondary batteries using the positive electrode active materials of Sample 31 and Sample 32 at 4.6 V charging The capacitance is shown in FIG. 43(A), and the discharge capacity retention rate is shown in FIG. 43(B).

[0414] Compared to sample 32, which did not contain magnesium and fluorine, Sample 31, to which fluorine was added, showed extremely good cycle characteristics.

[0415] Next, the results of various analyses performed on Sample 31 are shown below.

[0416] <stem-fft> STEM images of a cross section near the surface of the positive electrode active material of Sample 31 are shown in FIGS. FIG. 44(B) is an enlarged STEM image of a part of FIG. 44(A). FIG. 45(B) is an enlarged HAADF-STEM image of a portion of FIG. 44(A).

[0417] As is clear from FIG. 45, the region of about 0.5 nm from the surface of the positive electrode active material is different from other regions. The difference in brightness was observed. This is magnesium, an element lighter than the transition metals. This was thought to be because there were many

[0418] In addition, the region from the surface of the positive electrode active material to about 0.5 nm or more and up to about 5 nm is considered to be the inner region. The regularity was different from that of the surface. This was thought to be due to the different crystal orientation in this region and the area further inside.

[0419] Figure 46(A) is a bright-field STEM image of the same area as Figure 45(B). The FFT (Fast Fourier Transform) image of the area shown by FFT1 is shown in FIG. 46(B). Some of the bright spots in the image are designated A, B, C, and O, as shown in Figure 46(B).

[0420] For the bright spots in the FFT image of the area shown in FFT1, the actual measured values ​​are OA, d=0.2 2 nm, OB was d=0.25 nm, and OC was d=0.23 nm. Also, ∠AOB=5 8°, ∠BOC=69°, ∠AOC=127°.

[0421] This is the ICDD (International Centre for Diffra Magnesium oxide (MgO) data in the I OA(200) d=0.21nm, OB(1 -11) d = 0.24 nm, OC(-1-11) d = 0.24 nm, ∠AOB = 55 ∠BOC=70°, ∠AOC=125°. Therefore, the area shown in FFT1 is It is a region having a rock-salt type crystal structure, and it was speculated to be an image of the

[0011] incidence.

[0422] Also, the FFT image of the area indicated by FFT2 in FIG. 46(A) is shown in FIG. 46(C). Some of the bright spots in the two images are designated A, B, C, and O, as shown in Figure 46(C).

[0423] For the bright spots in the FFT image of the area shown in FFT2, the actual measured values ​​are OA, d=0.2 5 nm, OB was d=0.21 nm, and OC was d=0.49 nm. Also, ∠AOB=2 6°, ∠BOC=57°, ∠AOC=83°.

[0424] This is based on the data for lithium cobalt oxide (LiCoO2) in the ICDD database ( OA(10-11) d=0.24nm, O B(10-14) d=0.20nm, OC(0003) d=0.47nm, ∠AOB = 25°, ∠BOC = 55°, ∠AOC = 80°. Therefore, the area shown in FFT2 The region has a layered rock-salt crystal structure, and is an image of the [-12-10] incidence. It was guessed.

[0425] Moreover, the FFT image of the region indicated by FFT3 in FIG. 46(A) is shown in FIG. 46(D). Some of the bright spots in the FFT3 image are designated as A, B, C, and O, as shown in Figure 46(D). .

[0426] For the bright spots in the FFT image of the area shown in FFT3, the actual measured values ​​are OA, d=0.2 1 nm, OB was d=0.26 nm, and OC was d=0.24 nm. Also, ∠AOB=5 6°, ∠BOC=72°, ∠AOC=128°.

[0427] This is based on the data for lithium cobalt oxide (LiCoO2) in the ICDD database ( OA(01-14) d=0.20nm, O B(10-1-2)d=0.23nm, OC(1-102)d=0.23nm, ∠A OB=55°, ∠BOC=70°, ∠AOC=125° are close. Therefore, The region shown here has a layered rock-salt crystal structure and is an image of the [02-21] incidence. It was speculated that:

[0428] In other words, the regions shown in FFT2 and FFT3 have the same layered rock-salt crystal structure, but It became clear that these were regions with different crystal axis directions.

[0429] Also, in the range that can be observed in Figures 45(A), 45(B) and 46(A), the brightness Although the crystal orientations were different, they were observed to be roughly consistent.

[0430] Figure 47 shows the structure near the surface of the positive electrode active material, which is inferred from the results of STEM-FFT. The EM image is also shown. In Figure 47, M represents nickel, manganese, or cobalt.

[0431] The FFT3 region, which is the inner region of the positive electrode active material, has a layered rock salt type crystal structure. This is an image of the [02-21] incidence, in which the atoms of Mu and M are observed overlapping.

[0432] In addition, the FFT2 region, which is the surface layer of the positive electrode active material, has a layered rock salt type crystal structure. A layer of oxygen atoms, a layer of M (nickel, manganese, or cobalt) atoms, and a layer of lithium This is an image of the [-12-10] incidence, where the repeated layers of electron atoms can be observed. The repeated dark and light layers in the TEM image are due to the M layer and the oxygen and This is probably due to the repeated lithium layers. It has the same layered rock salt type crystal structure, but the direction of the crystal axes is different.

[0433] In addition, in the surface layer region of the positive electrode active material, FFT1, which is closer to the surface than FFT2, It has a rock-salt type crystal structure and is an image of the

[0011] incidence.

[0434] <edx> Next, the cross section near the surface of the positive electrode active material of sample 31 was analyzed using EDX. 48 and 49.

[0435] Fig. 48(A-1) is a HAADF-STEM image, Fig. 48(A-2) is an oxygen mapping. 48(B-1) is the mapping of magnesium, and 48(B-2) is the mapping of fluorine. Also, Figure 49(A-1) is the same HAADF-STEM image as Figure 48(A-1), and Figure 49 (A-2) is the mapping of manganese, Fig. 49 (B-1) is the mapping of nickel, Fig. 49 (B-2) is the mapping of cobalt.

[0436] First, from Figure 48(B-1), magnesium is concentrated in a region of about 3 nm from the surface of the positive electrode active material. It was observed that the ion exchange reaction was being analyzed. From the comparison of -2), it can be seen that there is less manganese in the surface layer of the positive electrode active material than in the interior, and It was observed that there was a region with a high concentration of cobalt and Cr. This region was about 5 nm from the surface. This region almost overlaps with the region in which a different regularity from the interior was observed in the STEM image.

[0437] Therefore, in sample 31, the positive electrode active material has a region having magnesium in the surface layer portion, and It was confirmed that the positive electrode active material had a region with a low manganese content in a part of the .

[0438] Considering the above results, the molar ratio of the starting material is LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2 A sample made by heating at 800℃ with +1mol%MgO+2mol%LiF It was revealed that the positive electrode active material No. 31 has the following characteristics.

[0439] First, the positive electrode active material of sample 31 has a second region having magnesium oxide in the surface layer. The inner part has a layered rock-salt type crystal structure, and the inner part has LiNi x Mn y Co z O2(x+y+z=1) and layered rock salt type crystals near the surface. LiNi with crystal structure a Mn b Co c O2(a+b+c=1) and a region having do.

[0440] LiNi inside x Mn y Co z O2 and LiNi a Mn b Co c O2 is the same layered salt structure. They have a crystal structure, but the orientation of the crystal axes may differ.

[0441] In addition, the content of each element is y>b, and the sum of nickel, manganese, and cobalt is In contrast, the manganese content may be low in regions close to the surface.

[0442] The positive electrode active material of sample 31 having the above characteristics is extremely suitable for use in secondary batteries. It shows good cycle characteristics. EXAMPLES

[0443] In this example, cobalt is used as the transition metal, and magnesium and fluorine are used as the starting materials. The results of EELS analysis of the positive electrode active material prepared by adding .

[0444] The sample of Example 1 was prepared by adding 1 mol% MgO and 2 mol% LiF as starting materials. Ple 7 was used as the analytical sample in this example.

[0445] The state of cobalt at six analysis points, *1 to *6, in the cross section of sample 7 was analyzed by EELS. FIG. 50 shows the vicinity of the surface of the positive electrode active material of sample 7 used in the EELS analysis. The cross-sectional STEM image is shown with *1 (depth of about 1 nm from the surface) and *2 (depth of about 2.5 nm from the surface). The analysis points are shown at *3 (approximately 5 nm) and *4 (approximately 10 nm from the surface of the positive electrode active material). m, *5 is approximately 100 nm from the surface of the positive electrode active material, *6 is near the center of the particle of the positive electrode active material .

[0446] The EELS spectrum intensity ratios of the cobalt L2 and L3 levels at each analysis point are shown in Table 1. 2 and Figure 51. The higher the L3 / L2 ratio, the lower the valence of cobalt.

[0447] [Table 12]

[0448] As is clear from Table 12 and FIG. 51, the L3 of the analysis point *1 closest to the surface of the positive electrode active material The highest L3 / L2 was 4.6. Also, the L3 / L2 from analysis point *2 to analysis point *6 was 4.6. *It was lower than 1 and in the range of 2.9 to 3.2, so no significant difference was observed.

[0449] From these results, it is clear that at the analysis point*1, cobalt exists in the divalent form as cobalt oxide (CoO). It was estimated that there was a lot of cobalt. In addition, from analysis point *2 to analysis point *6, lithium cobalt oxide It was speculated that most of the cobalt exists in trivalent form as lithium (LiCoO2). [Explanation of symbols]

[0450] 100 Cathode active material 101 First Area 102 Second Area 103 The Third Region 200 Active material layer 201 Graphene Compounds 211a positive electrode 211b negative electrode 212a Lead 212b Lead 214 Separator 215a Joint 215b Joint 217 Fixing member 250 batteries 251 Exterior body 261 Bending part 262 Seal part 263 Seal Part 271 Ridgeline 272 Valley Line 273 Space 300 Secondary battery 301 Positive electrode can 302 Anode can 303 Gasket 304 Positive electrode 305 Positive electrode current collector 306 Positive electrode active material layer 307 Negative electrode 308 Negative electrode current collector 309 Negative electrode active material layer 310 Separator 500 secondary battery 501 Positive electrode current collector 502 Positive electrode active material layer 503 Positive electrode 504 Negative electrode current collector 505 Negative electrode active material layer 506 negative electrode 507 Separator 508 Electrolyte 509 Exterior body 510 Positive lead electrode 511 Negative lead electrode 600 Secondary battery 601 Positive electrode cap 602 Battery Can 603 Positive terminal 604 Positive electrode 605 Separator 606 negative electrode 607 Negative terminal 608 Insulating plate 609 Insulating plate 611 PTC element 612 Safety valve mechanism 900 Circuit Board 910 Label 911 Terminal 912 Circuit 913 Secondary battery 914 Antenna 915 Seal 916 layers 917 layers 918 Antenna 920 Display device 921 Sensor 922 Terminal 930 Case 930a Case 930b Case 931 negative electrode 932 Positive electrode 933 Separator 950 Wound body 951 Terminal 952 Terminal 980 Secondary battery 993 Wound body 994 negative electrode 995 positive electrode 996 Separator 997 Lead Electrode 998 Lead Electrode 1001 Crystal Defects 7100 Portable display devices 7101 Case 7102 Display section 7103 Operation button 7104 Secondary battery 7200 Portable Information Terminal 7201 Case 7202 Display section 7203 Band 7204 Buckle 7205 Operation button 7206 Input / output terminal 7207 Icon 7300 display device 7304 Display section 7400 Mobile Phone 7401 Case 7402 Display section 7403 Operation button 7404 External connection port 7405 Speaker 7406 Mike 7407 Secondary battery 7408 Lead electrode 7409 Current collector 8000 display device 8001 Case 8002 Display section 8003 Speaker section 8004 Secondary battery 8021 Charging device 8022 Cable 8024 Secondary battery 8100 Lighting equipment 8101 Case 8102 Light source 8103 Secondary battery 8104 Ceiling 8105 Side wall 8106 Bed 8107 Window 8200 indoor unit 8201 Case 8202 Ventilator 8203 Secondary battery 8204 Outdoor unit 8300 Electric refrigerator-freezer 8301 Case 8302 Refrigerator door 8303 Freezer door 8304 Secondary battery 8400 Automobiles 8401 Headlight 8406 Electric Motor 8500 Automobiles 8600 Scooter 8601 Side mirror 8602 Secondary battery 8603 Turn signal light 8604 Under-seat storage 9600 Tablet PC 9625 Switch 9626 Switch 9627 Power Switch 9628 Operation Switch 9629 Fastener 9630 Case 9630a Case 9630b Case 9631 Display section 9633 Solar Cells 9634 Charge / discharge control circuit 9635 Electric storage unit 9636 DC-DC Converter 9637 Converter 9640 Moving parts< / edx> < / xps> < / stem>

Claims

1. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region includes magnesium oxide having a rock-salt crystal structure, CoO(II), and fluorine; the second region has more electron energy loss spectroscopy analysis points where divalent cobalt is present than trivalent cobalt; A part of magnesium contained in the magnesium oxide is bonded to fluorine, The electrolyte of the electrolytic solution contains lithium hexafluorophosphate, The electrolyte solution contains ethylene carbonate, diethyl carbonate, and vinylene carbonate, the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

2. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region includes magnesium oxide having a rock-salt crystal structure, CoO(II), and fluorine; the L2 level of cobalt measured by electron energy loss spectroscopy is L2 and the L3 level of cobalt is L3, the second region has analysis points where L3 / L2 is 3.8 or more; A part of magnesium contained in the magnesium oxide is bonded to fluorine, The electrolyte of the electrolytic solution contains lithium hexafluorophosphate, The electrolyte solution contains ethylene carbonate, diethyl carbonate, and vinylene carbonate, the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

3. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region includes magnesium oxide having a rock-salt crystal structure, CoO(II), and fluorine; The second region has more divalent cobalt than the first region, A part of magnesium contained in the magnesium oxide is bonded to fluorine, The electrolyte of the electrolytic solution contains lithium hexafluorophosphate, The electrolyte solution contains ethylene carbonate, diethyl carbonate, and vinylene carbonate, the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

4. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region includes magnesium oxide having a rock-salt crystal structure, CoO(II), and fluorine; the second region has more electron energy loss spectroscopy analysis points where divalent cobalt is present than trivalent cobalt; A part of oxygen contained in the magnesium oxide is replaced with fluorine, The electrolyte of the electrolytic solution contains lithium hexafluorophosphate, The electrolyte solution contains ethylene carbonate, diethyl carbonate, and vinylene carbonate, the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

5. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region includes magnesium oxide having a rock-salt crystal structure, CoO(II), and fluorine; the L2 level of cobalt measured by electron energy loss spectroscopy is L2 and the L3 level of cobalt is L3, the second region has analysis points where L3 / L2 is 3.8 or more; A part of oxygen contained in the magnesium oxide is replaced with fluorine, The electrolyte of the electrolytic solution contains lithium hexafluorophosphate, The electrolyte solution contains ethylene carbonate, diethyl carbonate, and vinylene carbonate, the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

6. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region includes magnesium oxide having a rock-salt crystal structure, CoO(II), and fluorine; The second region has more divalent cobalt than the first region, A part of oxygen contained in the magnesium oxide is replaced with fluorine, The electrolyte of the electrolytic solution contains lithium hexafluorophosphate, The electrolyte solution contains ethylene carbonate, diethyl carbonate, and vinylene carbonate, the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

7. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region includes magnesium oxide having a rock-salt crystal structure, CoO(II), and fluorine; the second region has more electron energy loss spectroscopy analysis points where divalent cobalt is present than trivalent cobalt; In the second region, the distribution of fluorine has an overlapping region with the distribution of magnesium; The electrolyte of the electrolytic solution contains lithium hexafluorophosphate, The electrolyte solution contains ethylene carbonate, diethyl carbonate, and vinylene carbonate, the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

8. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region includes magnesium oxide having a rock-salt crystal structure, CoO(II), and fluorine; the L2 level of cobalt measured by electron energy loss spectroscopy is L2 and the L3 level of cobalt is L3, the second region has analysis points where L3 / L2 is 3.8 or more; In the second region, the distribution of fluorine has an overlapping region with the distribution of magnesium; The electrolyte of the electrolytic solution contains lithium hexafluorophosphate, The electrolyte solution contains ethylene carbonate, diethyl carbonate, and vinylene carbonate, the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

9. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region includes magnesium oxide having a rock-salt crystal structure, CoO(II), and fluorine; The second region has more divalent cobalt than the first region, In the second region, the distribution of fluorine has an overlapping region with the distribution of magnesium; The electrolyte of the electrolytic solution contains lithium hexafluorophosphate, The electrolyte solution contains ethylene carbonate, diethyl carbonate, and vinylene carbonate, the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

10. In any one of claims 1 to 9, The CoO(II) forms a solid solution with the magnesium oxide. Lithium-ion secondary battery.

11. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region has a rock-salt crystal structure and contains magnesium, cobalt, oxygen, and fluorine; the second region has more electron energy loss spectroscopy analysis points where divalent cobalt is present than trivalent cobalt; a part of magnesium contained in the second region is bonded to fluorine; The electrolyte comprises vinylene carbonate; the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

12. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region has a rock-salt crystal structure and contains magnesium, cobalt, oxygen, and fluorine; the L2 level of cobalt measured by electron energy loss spectroscopy is L2 and the L3 level of cobalt is L3, the second region has analysis points where L3 / L2 is 3.8 or more; a part of magnesium contained in the second region is bonded to fluorine; The electrolyte comprises vinylene carbonate; the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

13. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region has a rock-salt crystal structure and contains magnesium, cobalt, oxygen, and fluorine; The second region has more divalent cobalt than the first region, a part of magnesium contained in the second region is bonded to fluorine; The electrolyte comprises vinylene carbonate; the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

14. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region has a rock-salt crystal structure and contains magnesium, cobalt, oxygen, and fluorine; the second region has more electron energy loss spectroscopy analysis points where divalent cobalt is present than trivalent cobalt; a part of oxygen contained in the second region is replaced with fluorine; The electrolyte comprises vinylene carbonate; the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

15. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region has a rock-salt crystal structure and contains magnesium, cobalt, oxygen, and fluorine; the L2 level of cobalt measured by electron energy loss spectroscopy is L2 and the L3 level of cobalt is L3, the second region has analysis points where L3 / L2 is 3.8 or more; a part of oxygen contained in the second region is replaced with fluorine; The electrolyte comprises vinylene carbonate; the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

16. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region has a rock-salt crystal structure and contains magnesium, cobalt, oxygen, and fluorine; The second region has more divalent cobalt than the first region, a part of oxygen contained in the second region is replaced with fluorine; The electrolyte comprises vinylene carbonate; the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

17. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region has a rock-salt crystal structure and contains magnesium, cobalt, oxygen, and fluorine; the second region has more electron energy loss spectroscopy analysis points where divalent cobalt is present than trivalent cobalt; In the second region, the distribution of fluorine has an overlapping region with the distribution of magnesium; The electrolyte comprises vinylene carbonate; the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

18. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region has a rock-salt crystal structure and contains magnesium, cobalt, oxygen, and fluorine; the L2 level of cobalt measured by electron energy loss spectroscopy is L2 and the L3 level of cobalt is L3, the second region has analysis points where L3 / L2 is 3.8 or more; In the second region, the distribution of fluorine has an overlapping region with the distribution of magnesium; The electrolyte comprises vinylene carbonate; the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

19. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region has a rock-salt crystal structure and contains magnesium, cobalt, oxygen, and fluorine; The second region has more divalent cobalt than the first region, In the second region, the distribution of fluorine has an overlapping region with the distribution of magnesium; The electrolyte comprises vinylene carbonate; the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

20. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region has a rock-salt crystal structure and contains magnesium, cobalt, oxygen, and fluorine; the second region has more electron energy loss spectroscopy analysis points where divalent cobalt is present than trivalent cobalt; a part of magnesium contained in the second region is bonded to fluorine; the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

21. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region has a rock-salt crystal structure and contains magnesium, cobalt, oxygen, and fluorine; the L2 level of cobalt measured by electron energy loss spectroscopy is L2 and the L3 level of cobalt is L3, the second region has analysis points where L3 / L2 is 3.8 or more; a part of magnesium contained in the second region is bonded to fluorine; the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

22. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region has a rock-salt crystal structure and contains magnesium, cobalt, oxygen, and fluorine; The second region has more divalent cobalt than the first region, a part of magnesium contained in the second region is bonded to fluorine; the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

23. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region has a rock-salt crystal structure and contains magnesium, cobalt, oxygen, and fluorine; the second region has more electron energy loss spectroscopy analysis points where divalent cobalt is present than trivalent cobalt; a part of oxygen contained in the second region is replaced with fluorine; the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

24. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region has a rock-salt crystal structure and contains magnesium, cobalt, oxygen, and fluorine; the L2 level of cobalt measured by electron energy loss spectroscopy is L2 and the L3 level of cobalt is L3, the second region has analysis points where L3 / L2 is 3.8 or more; a part of oxygen contained in the second region is replaced with fluorine; the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

25. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region has a rock-salt crystal structure and contains magnesium, cobalt, oxygen, and fluorine; The second region has more divalent cobalt than the first region, a part of oxygen contained in the second region is replaced with fluorine; the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

26. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region has a rock-salt crystal structure and contains magnesium, cobalt, oxygen, and fluorine; the second region has more electron energy loss spectroscopy analysis points where divalent cobalt is present than trivalent cobalt; In the second region, the distribution of fluorine has an overlapping region with the distribution of magnesium; the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

27. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region has a rock-salt crystal structure and contains magnesium, cobalt, oxygen, and fluorine; the L2 level of cobalt measured by electron energy loss spectroscopy is L2 and the L3 level of cobalt is L3, the second region has analysis points where L3 / L2 is 3.8 or more; In the second region, the distribution of fluorine has an overlapping region with the distribution of magnesium; the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

28. The battery has a positive electrode, a negative electrode, and an electrolyte solution, The positive electrode has a positive electrode active material including lithium cobalt oxide, The positive electrode active material has a first region and a second region outside the first region, The first region has a layered rock salt type crystal structure, the second region has a rock-salt crystal structure and contains magnesium, cobalt, oxygen, and fluorine; The second region has more divalent cobalt than the first region, In the second region, the distribution of fluorine has an overlapping region with the distribution of magnesium; the second region has a region in contact with a decomposition product of the electrolyte, The negative electrode has a negative electrode active material containing carbon. Lithium-ion secondary battery.

29. In any one of claims 1 to 28, The fluorine contained in the second region is in contact with a decomposition product of the electrolyte. Lithium-ion secondary battery.

30. In any one of claims 1 to 29, When the surface of the positive electrode active material is analyzed by XPS, the ratio of the magnesium concentration to the fluorine concentration satisfies Mg:F=y:1 (3≦y≦5) (atomic ratio). Lithium-ion secondary battery.

31. In any one of claims 1 to 30, When the surface of the positive electrode active material is subjected to XPS analysis, the peak position of the fluorine bond energy is 682 eV or more and less than 685 eV. Lithium-ion secondary battery.

32. In any one of claims 1 to 31, When the surface of the positive electrode active material was analyzed by XPS, the peak position of the fluorine binding energy was about 684.3 eV. Lithium-ion secondary battery.

33. In any one of claims 1 to 32, The electrolyte used is a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 3:7, with vinylene carbonate added at 2% by weight. Lithium-ion secondary battery.

34. In any one of claims 1 to 33, a magnesium concentration peak is detected within 2 nm from the surface of the positive electrode active material by energy dispersive X-ray analysis of the positive electrode active material; Lithium-ion secondary battery.

35. In any one of claims 1 to 34, a magnesium concentration peak is detected by energy dispersive X-ray analysis of the positive electrode active material; The second region is a region from the surface of the positive electrode active material to where the peak becomes 1 / 5. Lithium-ion secondary battery.

36. In any one of claims 1 to 35, A fluorine concentration peak is detected within 1 nm from the surface of the positive electrode active material by energy dispersive X-ray analysis of the positive electrode active material. Lithium-ion secondary battery.

37. In any one of claims 2, 5, 8, 12, 15, 18, 21, 24 and 27, The first region has analysis points where L3 / L2 is less than 3.

8. Lithium-ion secondary battery.

38. In any one of claims 1 to 37, The first region contains more trivalent cobalt than other valences of cobalt, The second region has more divalent cobalt than other valences of cobalt. Lithium-ion secondary battery.

Citation Information

Patent Citations

  • Positive electrode active material for lithium secondary battery, manufacturing method thereof, and lithium secondary battery

    JP2009026640A

  • Power storage device

    JP2012018914A

  • Positive electrode active material for lithium ion secondary battery, and lithium ion secondary battery

    JP2016076454A